Ecological regime shifts decouple organic carbon sequestration from nutrient-driven productivity in Anthropocene shallow lakes - Shixin Huang; Ke Zhang; Wenwei Zhao; Qi Lin; David Taylor; Ji Shen (Global and Planetary Change, 2026)

Characterizing effects of tree mortality from wildfire and bark beetles using satellite observations of solar-induced chlorophyll fluorescence - Lewis Kunik; David R. Bowling; Brett Raczka; Jeffrey A. Hicke; Christian Frankenberg; Rui Cheng; Michèle R. Slaton; John C. Lin (Remote Sensing of Environment, 2026)

Substitution of solid fats in model baked foods using emulsion-templated oleogels: Effects on microstructure, texture, and flavor - Junqing Han; Wenbo Miao; Qianzhu Lin; David Julian McClements; Keyu Lu; Zhengyu Jin; Zhitao Li; Chao Qiu (Food Bioscience, 2026)

Vanadium salt inhibits osteoclast formation and preserves bone integrity in a rat model of type-1 diabetes associated bone loss - Joshua Greendyk; James Thornton; Darian Napoleon; Michael Greenberg; Anthony Lin; Mike Levidy; Jonathan R. Lopez; Maximilian Muñoz; Kevin Innella; Yazan Kadkoy; Maya Deza Culbertson; Jessica A. Cottrell; et al. (BioMetals, 2026)

Accelerating wastewater-based SARS-CoV-2 surveillance using a mobile laboratory in mixed infrastructure regions - Amirmohammad Sakhaei; Soroosh Torabi; Mohammad Dehghan Banadaki; Alexus Rockward; William D. Strike; Soroush Farahbakhsh; David Graf; August Bodin; Amanda Muzzey; Riley Lang; Sara Ignoffo; Sean Haley; et al. (Science of The Total Environment, 2026)

Associations of Placental Oxidative Stress with Exposure to Gestational Air Pollution: Evidence from the UPSIDE Cohort - Emily A. Craig; Yan Lin; Yihui Ge; Xiangtian Wang; Otgondelger Enkhtaivan; Don K. Harrington; Richard K. Miller; Susan K. Murphy; Sally W. Thurston; Philip K. Hopke; Emily S. Barrett; Thomas G. O'Connor; et al. (Environmental Research, 2026)

Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Toward improved conservation risk assessments in the marine aquarium fish trade: Reply to Biondo and Calado (2026) - Bing Lin; Andrew L. Rhyne; Michael Tlusty; Yiwen Zeng; Bryan To; Robert J. Holmberg; David S. Wilcove (Conservation Biology, 2026)

Dietary Patterns Associated With Weight Loss Among Patients With Colorectal Cancer During the First 6 Months After Diagnosis: A Cross-Sectional Analysis From the ColoCare Study - Rachel Hoobler; Fred K. Tabung; Tengda Lin; Biljana Gigic; Kristen S. Smith; Kary Woodruff; Sylvia L. Crowder; Sheetal Hardikar; Doratha A. Byrd; Adriana M. Coletta; Alejandro Sanchez; Amandine Chaix; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Structural and functional characterization of pectic polysaccharide fractions isolated from Choerospondias axillaris flesh - Qian Li; Rui Kang; Hongyi Lin; Yuanhang Wan; Taotao Dai; Panting Tian; Huashan Ling; David Julian McClements; Peiyi Shen; Jun Chen (Food Chemistry, 2026)

Learn to listen and listen to learn: reflections from a co-production process between researchers and composers - Carolin Seiferth; Agnes B. Olin; Konstantinos-Marios Vaziourakis; Sriharsha Bhat; Åsa N. Austin; Christina Lin; Sampo Kasurinen; Zacharias Ehnvall; Mioko Yokoyama; Maya Miro Johnson; Anna Berg; David Tudén; et al. (Sustainability Science, 2026)
As platforms for dialogue, art-science collaborations hold the potential to cross disciplinary boundaries to better understand and engage the public in addressing sustainability challenges. Moving beyond documenting outcomes, this study details how researchers and composers combined science communication and artistic expression to co-produce performances as part of the Baltic Sea Festival Science Lab. Drawing on insights from a joint reflection process, we recount our motivations for participation, provide insights on the co-production processes of six researcher-composer pairs, and share our experiences of the performances. We highlight openness to other ways of working, different perspectives and opinions, and emergence as well as collaborative skills, including listening, communication, and problem-solving skills, as key enablers for crossing disciplinary boundaries in art-science collaborations. As answers to the question on how, why, and in what ways platforms for dialogue can turn into platforms for learning, we discuss opportunities for designing safe-enough spaces, working towards a shared goal while embracing the unfolding nature of a process, and engaging in reflection to follow up on and make sense of one’s learning. Through this study, we hope to provide guidance for those who wish to engage in art-science collaborations to co-produce pathways towards sustainable futures together.

Building trust in the integration of artificial intelligence into chemical risk assessment: findings from the 2024 ECETOC workshop - Timothy W. Gant; Alistair Boxall; Daniel Burgwinkel; Maryam Zare Jeddi; Ivo Djidrovski; Steffi Friedrichs; Barry Hardy; Thomas Hartung; Daniela Holland; Andreas Karwath; Anne Kienhuis; Nicole Kleinstreuer; et al. (Archives of Toxicology, 2026)
Artificial Intelligence (AI) is increasingly influencing chemical risk assessment, enabling faster, more comprehensive, and potentially more ethical assessments. The application of AI in chemical risk assessment refers to both generative and predictive algorithms encompassing machine learning, to analyse complex chemical, biological, and environmental data and provide insights into adverse effect potential for humans and ecosystems. AI systems support the prediction of chemical hazards, exposure levels, and adverse effects by learning from experimental results, mechanistic models, and regulatory datasets, thereby enhancing the efficiency of safety evaluations. In October 2024, ECETOC held an international workshop, with experts from academia, industry, and regulatory bodies, to reflect upon the historical challenges in integrating multidimensional omics technologies into chemical regulation and explore the current capabilities and future potential of AI in toxicology and regulatory science. Discussions emphasised that implementation of Findable, Accessible, Interoperable, and Reusable (FAIR) data principles is not just a best practice but rather a prerequisite for building transparent, reliable, and unbiased AI systems. The reliability of AI in producing scientifically valid and socially responsible outcomes depends fundamentally on the availability of FAIR data. However, ensuring trustworthiness also requires robust governance frameworks that go beyond data and human oversight. Critical enablers of responsible AI in chemical risk assessment are rigorous governance, explainability, fit-for-purpose applications, and human oversight. ECETOC supports the development of flexible and iterative frameworks advancing development, validation, transparency, accountability, and trust in AI applications in chemicals regulation.

Host and Environmental Drivers of Gut Microbiome Variation in Wild Anolis Lizards - Yanileth F. López Tacoaman; Maria Alcivar; Karla Alujević; Leah Bakewell; John David Curlis; Anabarbara Gonzalez; Noah D. Gripshover; Samir Gulati; Renata M. Pirani; Noa Ratia; Daniel Romero; Kelly Lin Wuthrich; et al. (Molecular Ecology, 2026)
Animals maintain close associations with diverse microbiota that inhabit their digestive tracts, and these associations can profoundly affect host physiology and fitness. Gut microbiome composition is shaped by both host traits and environmental factors, yet the relative importance of these forces remains unclear in many taxa, including squamate reptiles (lizards and snakes). To address this gap, we analysed the gut microbiomes of seven species of Anolis lizards in the lowland tropical rainforest of central Panama. We sought to determine how environmental and host species characteristics shaped gut microbiome composition. Specifically, we examined (1) interspecific variation in the anole gut microbiome, (2) the relative roles of environment and host species in shaping gut microbiomes across two study locations, and (3) patterns of phylosymbiosis. We found that host‐related factors (species identity, body size, and phylogenetic distance) were significant predictors of the composition of Anolis gut microbiomes. However, environmental factors, including locality and year of sampling (associated with temperature, humidity, and precipitation), also exerted significant effects. We detected evidence of phylosymbiosis, but this pattern was moderate, possibly due to the strong effect of environmental variation. Our work contributes to the growing body of literature on lizard gut microbiomes by using comparative observations across habitats and species to identify the factors that shape these communities in the wild.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Full Manure Recycling Risks an 18% Rise in China's Cropland N 2 O Emissions Without Improved Management - Shidi Ba; Zhaohai Bai; Lin Ma; Davey L. Jones; David R. Chadwick (Global Change Biology, 2026)
Cropland fertilization is the largest anthropogenic source of nitrous oxide (N 2 O‐N) emissions in China and could be mitigated through manure substitution. However, accurate quantification of N 2 O‐N losses under different combinations of manure and chemical fertilizer applications remains challenging due to limited national data, oversimplified methods of estimation, and neglect of the nitrogen (N) source (chemical‐N and manure‐N) interaction effects under mixed fertilization on N 2 O‐N production processes. Using a dataset consisting of 2186 observations across China, we developed N 2 O‐N models for fertilized (chemical fertilizer and manures) croplands incorporating climate, soil, fertilization and cropping variables, with particular emphasis on the manure component, through machine‐learning approaches. Model simulations estimated a median N 2 O‐N flux of 1.1 kg ha −1 and a total national N 2 O‐N loss of 243.7 Gg in 2019, with a hotspot in Northcentral China. During 2000–2019, N 2 O‐N losses were driven mainly by annual total N input. By 2050, merely pursuing 100% manure recycling without considering improved manure‐N use efficiency could lead to an 18% increase in N 2 O‐N losses compared with 2019. Hence, this study provides a high‐resolution modeling framework to predict how developments in manure substitution will affect the magnitude and spatial distribution of N 2 O‐N losses. We also demonstrate that future manure substitution policies will need to promote improved manure nutrient management at the same time as greater manure recycling rates.

Increased Soil Carbon and Nitrogen Stocks Associate With Stronger Calcium–Microbial and Multi‐Trophic Interactions Under Warming - Dan Xiao; Wei Zhang; David R. Johnson; Peilei Hu; Lin Xu; Mingming Sun; Li Tang; Xunyang He; Jie Zhao; Xionghui Liao; Wanxia Peng; Hongsong Chen; et al. (Global Change Biology, 2026)
Converting cropland to planted forests improves soil organic carbon (SOC) and total nitrogen (TN) storage while contributing to climate change mitigation, primarily through the regulation of belowground organisms and mineral protection such as calcium (Ca). However, the mechanistic pathways linking exchangeable Ca 2+ , soil micro‐food web interactions, and nutrient accumulation under warming remain unclear. Here, we investigated their potential roles in driving the accumulation of mineral‐associated organic matter (MAOM), SOC, and TN in planted forests compared with croplands under warming conditions. Planted forests exhibited higher MAOM, SOC, and TN than cropland and had stronger coupling between carbon and nitrogen. Warming increased MAOM, SOC, and TN in planted forests but reduced SOC in cropland. Compared to cropland, planted forests displayed elevated levels of soil exchangeable Ca 2+ , microbial necromass carbon and nitrogen, stronger Ca–microbial and multi‐trophic associations. Warming further amplified positive Ca–microbial (e.g., bacteria and fungi) and cross‐trophic associations (e.g., nematode–bacteria, nematode–fungi, nematode–protist, and omnivore‐predator–bacteria/fungi) in planted forests by increasing plant productivity, litter biomass, and soil exchangeable Ca 2+ , whereas cropland showed limited responsiveness to temperature changes. In planted forests, soil exchangeable Ca 2+ was positively correlated with Ca–microbial and cross‐trophic associations, microbial necromass carbon and nitrogen, and the contents of MAOM, SOC, and TN. These relationships were absent in cropland. Notably, cross‐trophic associations rather than microbial abundance or diversity, with significant modulation by soil exchangeable Ca 2+ , had the strongest positive relationship with MAOM, SOC, and TN accumulation in planted forests. Collectively, our findings lead to the hypothesis that warming promotes SOC and TN storage in planted forests by jointly strengthening exchangeable Ca 2+ , Ca–microbial and cross‐trophic interactions. These results highlight the potential importance of multi‐trophic interactions and Ca‐mediated processes in stabilizing microbial necromass and fostering carbon and nitrogen preservation during vegetation restoration in response to warming.

Ecological regime shifts weaken sedimentary carbon sequestration in shallow Lake liangzi - Jinglin Hou; Qi Lin; Jiasheng Zhang; Shixin Huang; Yuan Jin; Yanhua Wang; Haibo He; Pierre Taillardat; David Taylor; Ke Zhang; Michael E. Meadows (Water Research, 2026)

Two-stage Jurassic tectono-geomorphological evolution of the Yili-Central Tianshan: Insights into its role in shaping the Mesozoic-Cenozoic Landscape - Dunfeng Xiang; Qigui Mao; Zhiyong Zhang; Songyan Liu; David Chew; Lin Wu; Nan Wang; Chao Guo; He Yang; Wenjiao Xiao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Plasmid-mediated modulation of Listeria monocytogenes biofilm formation via TCS/PTS signaling: Implications for food contamination control - Jing Wang; Hui-Min David Wang; Yang Qu; Ting Lin; Changyan Zhou; Zijie Lin; Yangtai Liu; Zhuosi Li; Qingli Dong; Yujuan Suo (Food Research International, 2026)

Preparation-controlled structural modulation of starch nanoparticles and protein corona formation mechanisms - Han Hu; David Julian McClements; Qianzhu Lin; Hangyan Ji; Zhengyu Jin; Chao Qiu (Food Hydrocolloids, 2026)

Pilot-scale demonstration of a laminate-based CALF-20 rapid cycle pressure-vacuum swing adsorption process for carbon capture - Nicholas Stiles Wilkins; David Murray McKinnon; Chinmay Baliga; Tai Tran Thanh Nguyen; Bérénice Moroy; Ian Xu; Xilan Lin; Onder Tulpar; Nigel Wheeler; Victor Tran; Alireza Lotfollahzade Moghaddam; Desmond Cronin; et al. (Chemical Engineering Journal, 2026)

Calcite TLM as a new natural reference material for in situ U-Pb geochronology and its geological implications - Tianyi Li; Ranran Chen; Shitou Wu; Rolf L. Romer; Nick M.W. Roberts; Kerstin Drost; David Chew; Marcel Guillong; Qian Ma; Yahui Yue; Shuangjian Li; Bohang Xie; et al. (Chemical Geology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Advanced technologies of artery-on-a-chip: a review of construction strategies and disease models - Shi-Qi Chang; Li Qiao; Oluwatosin David Abodunrin; Lin Zou; Ning-Ping Huang (Angiogenesis, 2026)

Prenatal exposure to extreme heat and autism in children - David G. Luglio; Xin Yu; Jane C. Lin; Ting Chow; Mayra P. Martinez; Zhanghua Chen; Sandrah P. Eckel; Joel Schwartz; Frederick W. Lurmann; Nathan Pavlovic; Rob McConnell; Anny H. Xiang; et al. (Science of The Total Environment, 2026)

An analysis of population movements to characterize China's differentiated countryside: The case of Chengdu - Lin Tian; Xuchen Zhang; David Shaw; Peng Fu (Journal of Rural Studies, 2026)

Orbital forcing across a predominantly eolian record of the Eocene–Oligocene transition, Inner Mongolia, China - Ke Xu; Nan Wu; Jianye Ren; David B. Kemp; Lin Ye; Zhongheng Sun; Xiangrong Yang; Xianghui Zhang; Mingsong Li (Global and Planetary Change, 2026)

Feasibility of a Multi-Laboratory Model of Middle Cerebral Artery Thromboembolic Stroke with Thrombolysis: TE-MCAo - Michelle Lin; Mozammel Bhuiyan; Carly McCurry; Jessica Lamb; Marcio A. Diniz; Karni Bedirian; Anil K. Chauhan; Abhishek Jha; Aditi Jain; Enrique C. Leira; Rakeshkumar Patel; Mohammad B. Khan; et al. (Translational Stroke Research, 2026)
No single animal stroke model satisfies all needs of translational stroke investigation. While the nylon filament model is widely accepted in preclinical translational stroke research, thromboembolic models have more physiological relevance. Thromboembolic models are technically difficult, time consuming, and show variable results, making them problematic for multi-laboratory preclinical network use. We sought to develop and validate a multi-laboratory thromboembolic middle cerebral artery occlusion model that encompasses vessel occlusion and subsequent thrombolysis. To reduce the numbers of donor animals used, we developed a method to store donor blood for later use. Using prefabricated microcatheters, we simplified thrombus preparation and handling. Emboli were prepared in microcatheters and injected directly into the middle cerebral artery from the internal carotid artery. For thrombolysis we used intravenous Tenecteplase dosing at 1.5 mg/kg. To demonstrate feasibility and ease-of-use, the model was implemented at six research laboratories. We wrote and field-tested standard operating procedures, training videos, and hands-on surgical training workshops. We enrolled 170 Sprague Dawley rats of both sexes at six laboratories who performed 4 to 6 thrombus embolizations per week. All sites could achieve reproducible occlusion and thrombolysis. Thromboemboli prepared from stored blood served as well as emboli from freshly drawn blood. Of 135 rats who received one embolus, 33 (24%) died before 48-hour MRI scan. In survivors, stroke volume was 13 ± 16% of the ipsilateral hemisphere. Occlusions were seen in the MCA in 15%, distal ICA in 19%, both (T-occlusions) in 2% and in the MCA/ACA in 1%. Corner test, neurobehavioral battery, and MRI showed reasonably consistent stroke injury. We established the feasibility and reproducibility of a multi-laboratory rodent thromboembolic model but further development is needed to improve the success rate and lower the mortality rate before this model can be accepted widely.

Extent of threats to marine fish from the online aquarium trade in the United States - Bing Lin; Yiwen Zeng; Bryan To; Robert J. Holmberg; Andrew L. Rhyne; Michael Tlusty; David S. Wilcove (Conservation Biology, 2026)
The global marine aquarium hobby is a multibillion‐dollar industry, largely driven by demand from the United States. Much of this trade occurs online. We web scraped 4 major US‐based e‐commerce platforms selling marine aquarium fish to determine the retail price and source (wild capture, aquaculture, or both) of 13 families of ray‐finned marine fish ( Actinopterygii ). We supplemented this with ecological and economic trait data from FishBase and the International Union for Conservation of Nature (IUCN). Across all platforms and 13 popular fish taxonomic families, we found 734 unique species for sale, 89.2% (655 species) of which were sourced exclusively from the wild. A total of 45 species were of conservation concern (20 threatened species and 25 additional species with decreasing population trends), 38 of which were sourced solely from the wild. Retail price was significantly correlated with source, body length, minimum occupied depth, and schooling behavior. A further 100 species for sale were not listed as being in the aquarium trade in FishBase or by the IUCN, indicating incomplete information on this fishery in 2 important databases. For 58 species (encompassing 71 variants) with both wild‐caught and captive‐bred individuals for sale, aquaculture fish were a mean 28.1% (95% confidence interval 15.3) cheaper than their wild‐caught counterparts.

Hydrophobic neutral and basic fractions of organic fertilizer-derived dissolved organic matter promote phosphorus mobilization in paddy soils - Haibo Wang; Xipeng Liu; Songcan Chen; Chengliang Sun; David R. Chadwick; Davey L. Jones; Xianyong Lin (Soil and Tillage Research, 2026)

A least-squares spatio-temporal adjustment algorithm (LSSTAA) for radiometric normalization of PlanetScope time series - Lin Yan; David P. Roy; Haiyan Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Impact of low-emission driving behavior on brake wear PM emissions: insights from a real-world evaluation - Ye Liu; Tangjian Wei; Haibo Chen; Sijin Wu; Yili (Kelly) Tang; Zhiyuan Lin; David Watling; Jingwen Yao; Nansong Yue; Chenxi Wang; Dingsong Cui; Dimitris Margaritis (Transportation Research Part D: Transport and Environment, 2025)

Indian summer monsoon variability across the last 9000 years: New evidence from stalagmites of southwestern China - Yanzhen Li; Chunju Huang; Jianghu Lan; David B. Kemp; James G. Ogg; Ashish Sinha; Lvfan Chen; Xiqian Wang; Huiru Tang; Xu Lin; Khalaf H.M. Abdel-Raheem; Rui Zhang; et al. (Global and Planetary Change, 2025)

Prenatal air pollution exposure and placental vasculature development among participants of the UPSIDE cohort study - Shivram Kumar; Carolyn M. Salafia; Ruchit Shah; Theresa Girardi; Richard K. Miller; Sally W. Thurston; Philip K. Hopke; David Skrill; Jessica Brunner; Donald Harrington; Yihui Ge; Yan Lin; et al. (Environmental Research, 2025)

Retraction Note: Artificial intelligence-based solutions for climate change: a review - Lin Chen; Zhonghao Chen; Yubing Zhang; Yunfei Liu; Ahmed I. Osman; Mohamed Farghali; Jianmin Hua; Ahmed Al-Fatesh; Ikko Ihara; David W. Rooney; Pow-Seng Yap (Environmental Chemistry Letters, 2025)

Pre-surgery gut microbial diversity and abundance are associated with post-surgery onset of cachexia in colorectal cancer patients: the ColoCare Study - Mmadili N. Ilozumba; Maria F. Gomez; Tengda Lin; Caroline Himbert; June L. Round; W. Zac Stephens; Christy A. Warby; Sheetal Hardikar; Christopher I. Li; Jane C. Figueiredo; Victoria Damerell; Gary C. Fillmore; et al. (Cancer Causes & Control, 2025)
Background Cachexia accounts for about 20% of all cancer-related deaths and it is indicative of poor prognosis and progressive functional impairment. The role of the gut microbiome in the development of cachexia in colorectal cancer (CRC) patients has not been established. Methods Pre-surgical stool samples from n = 103 stage I–III CRC patients in the ColoCare Study were analyzed using 16S rRNA gene sequencing (Illumina) to characterize fecal bacteria. We calculated estimates of alpha- and beta-diversity and a priori- and exploratory-selected bacterial relative abundance. Using Fearon criteria, cachexia onset at 6 months post-surgery was defined as > 5% weight loss over the past 6 months and/or body mass index (BMI) of < 20 kg/m 2 and weight loss of > 2%. Associations of microbial metrics with cachexia onset were estimated using multivariable logistic regression models. Results Higher alpha-diversity was positively associated with cachexia onset, with stronger associations in females, patients < 65 years, those receiving adjuvant treatment, consuming high fiber, or with energy intake outside USDA recommendations ( p < 0.05). Porphyromonas (OR = 0.51, 95% CI 0.26–0.89, p = 0.03) and Actinomyces (OR = 0.72, 95% CI 0.48–1.03, p = 0.08) were inversely associated with cachexia, although the association for Actinomyces did not reach statistical significance. Stratified analyses revealed a stronger inverse association between Porphyromonas and cachexia onset in males, patients with rectal or stage III tumors, those receiving neoadjuvant treatment, physically inactive individuals, and those consuming low fiber. However, these associations did not reach statistical significance (0.05 ≤ p < 0.10). Conclusion Higher gut microbial alpha-diversity and lower relative abundances of the genera Porphyromonas and Actinomyces in pre-surgery stool samples were associated with onset of cachexia in CRC patients six months post-surgery. This is the first study to explore a link between the gut microbiome and cachexia in CRC patients, providing novel insights into the biology of cachexia and potential clinical interventions.

PM2.5 and NO2 exposure during pregnancy and measures of fetal size and attained size at birth - Nafisa Nawal Islam; Sally W. Thurston; Donald Harrington; Yihui Ge; Samuel Weisenthal; Jessica Brunner; Richard K. Miller; Philip K. Hopke; Yan Lin; Emily S. Barrett; Thomas G. O’Connor; Junfeng Zhang; et al. (Air Quality, Atmosphere & Health, 2025)

Silicon isotope variations of ocean island basalts: the effect of recycled materials on Si isotopes in the mantle - Yu-Chao Lin; Hui-Min Yu; Matthew G. Jackson; Elisabeth Widom; David Kuentz; Fang Huang (Geochimica et Cosmochimica Acta, 2025)

Analysis of source regions and transport pathways of sub-micron aerosol components in Europe - Michelle Y. Schneider; Jianhui Jiang; Ying Chen; Wenche Aas; Samira Atabakhsh; Minna Aurela; Claudio Belis; Aikaterini Bougiatioti; Michael Bressi; Francesco Canonaco; Benjamin Chazeau; Hasna Chebaicheb; et al. (Environmental Pollution, 2025)

Sex specific gut bacterial community structure: implications for frailty risk in people with HIV - Aline Zaparte; John W. Lammons; Christopher M. Taylor; Meng Luo; Hui-Yi Lin; Robert W. Siggins; Patricia E. Molina; David A. Welsh (GeroScience, 2025)

Effect of soil properties on microcystin mobility and bioavailability in land-applied drinking water treatment residuals - Ying-Ren Lai; Zhian Lin; David Tomashefski; Elizabeth A. Dayton; Shane W. Whitacre; Jiyoung Lee; Nicholas T. Basta (Science of The Total Environment, 2025)

Insufficient telomeric DNA damage response promotes chromosomal instability in aged oocytes - Tianqi Cao; Simiao Liu; Fang Wang; Min Gao; Wenlian Wu; Yanling Qiu; Ming Mu; Tengteng Xu; Jinkun Wen; Yuxi Chen; Haiying Liu; Xiqian Zhang; et al. (Science Bulletin, 2025)

Electron diffraction-guided natural product discovery: identification and isolation of new scaffold class from Podospora australis - David A. Delgadillo; Lin Wu; Jessica E. Burch; Lygia Silva de Moraes; Caroline Wang; Benjamin P. Tu; Yi Tang; Hosea M. Nelson (Phytochemistry Letters, 2025)

Exploring controls on precipitation-runoff dependencies: Implications for non-stationary and spatially heterogeneous analyses - Tian Lan; Xinyue Du; Xue Xie; Kairong Lin; Hongbo Zhang; Xinghui Gong; Yongqin David Chen; Chong-Yu Xu (Journal of Hydrology, 2025)

Improving C-phycocyanin photostability by forming complexes with organic acids: l-ascorbic acid, ferulic acid and cinnamic acid - Yuman Wang; Lei Zhou; Suyun Lin; Junbing Zhang; David Julian McClements; Shengfeng Peng; Wei Liu (Food Chemistry, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Stability prediction of multi-material complex slopes based on self-attention convolutional neural networks - Mansheng Lin; Xuedi Chen; Gongfa Chen; Zhiwei Zhao; David Bassir (Stochastic Environmental Research and Risk Assessment, 2025)

Population genomics of rainforest mountain frogs (Anura: Limnodynastidae: Philoria) severely impacted by the Australian megafires - Shengyao Lin; David Newell; Nicola J. Mitchell; Stephen C. Donnellan; Michael Mahony; Liam J. Bolitho; Renee A. Catullo (Conservation Genetics, 2025)
The 2019/20 Australian megafires impacted numerous species, including six of the seven montane frog species from the genus Philoria , which are restricted to the top of mountain habitats across eastern Australian Gondwana Rainforest. Using single nucleotide polymorphisms, we examined the population structure and genetic diversity of the six Philoria species to inform conservation management and assess their capacity for post-fire recovery. Narrow-range species were confirmed as a single population for management purposes, while P. kundagungan , P. loveridgei , and P. sphagnicolus exhibit marked genetic differentiation between populations, indicating strong allopatric differentiation among populations isolated on separate mountaintops, suggesting limited natural dispersal ability. We further identify high-value genetic populations in these structured species. Populations that were heavily impacted by the fires, such as P. pughi and P. knowlesi , may face longer-term threats due to potential declines in adaptive capacity. We recommend prioritising in situ management, genetic rescue, and translocation efforts to bolster resilience in isolated populations. Updated conservation planning and targeted fire buffer management are crucial for the survival of these ancient, regionally endemic frogs in a rapidly changing climate.

Robust strategy for bioplastic production from cyanobacteria-enriched microbiomes: insights from gene expression and population dynamics - Beatriz Altamira-Algarra; Lin Sun; David San León Granado; Lucía Romero-Morillo; Livia Vurro; Juan Nogales; Eva Gonzalez-Flo; Joan Garcia (Chemical Engineering Journal, 2025)

Genomic insights into the brooding reproduction and climate-driven dynamics of Pocillopora damicornis in the Anthropocene - Jie Li; Yali Liu; Zhixin Zhang; Yu Chen; Jian Zhang; Haiyan Yu; Yingyi Zhang; Cong Liu; Zhuang Shao; David G. Bourne; Meng Qu; Si Zhang; et al. (Science China Life Sciences, 2025)

Spinocerebellar Ataxia Type 27B can be Suspected Based on Clinical Phenotype: The Massachusetts General Hospital Ataxia Center Experience - Leigh A. Rettenmaier; Jin Yun Helen Chen; Jason MacMore; Anoopum S. Gupta; Chih-Chun Lin; Christopher D. Stephen; David Pellerin; Bernard Brais; Jeremy D. Schmahmann (The Cerebellum, 2025)

Drivers of state legislative actions restricting foreign holdings of U.S. agricultural land - Lin Lin; David L. Ortega (Food Policy, 2025)

Progress in using cross-linking technologies to increase the thermal stability of colloidal delivery systems - Wen Xu; Kuang He; Ziqiang Lin; David Julian McClements; Zhengyu Jin; Long Chen (Critical Reviews in Food Science and Nutrition, 2025)

Recent advances in enzymatic modification techniques to improve the quality of flour-based fried foods - Guifang Huang; David Julian McClements; Kuang He; Ziqiang Lin; Zipei Zhang; Ruojie Zhang; Zhengyu Jin; Long Chen (Critical Reviews in Food Science and Nutrition, 2025)

Effects of different polysaccharides on the formation, stability, and rheological properties of oleogels structured by octenyl succinic anhydride starch - Wenbo Miao; David Julian McClements; Jilong Wang; Zhiheng Zhang; Qianzhu Lin; Hangyan Ji; Zhengyu Jin; Chao Qiu (Food Chemistry, 2025)

Oleogels derived from modified starch-gelatin-tannic acid aerogel templates: Fabrication, characterization and application - Wenbo Miao; Weijie Zhou; David Julian McClements; Zhiheng Zhang; Qianzhu Lin; Hangyan Ji; Zhengyu Jin; Shangyuan Sang; Chao Qiu (Food Hydrocolloids, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Multi-model assessment of climate change impacts on drought characteristics - Adnan Dehghani; Fatemehsadat Mortazavizadeh; Amin Dehghani; Muhammad Bin Rahmat; Hadi Galavi; David Bolonio; Jing Lin Ng; Vahid Rezaverdinejad; Majid Mirzaei (Natural Hazards, 2025)

Predicting the impact of rare variants on RNA splicing in CAGI6 - Jenny Lord; Carolina Jaramillo Oquendo; Htoo A. Wai; Andrew G. L. Douglas; David J. Bunyan; Yaqiong Wang; Zhiqiang Hu; Zishuo Zeng; Daniel Danis; Panagiotis Katsonis; Amanda Williams; Olivier Lichtarge; et al. (Human Genetics, 2025)
Variants which disrupt splicing are a frequent cause of rare disease that have been under-ascertained clinically. Accurate and efficient methods to predict a variant’s impact on splicing are needed to interpret the growing number of variants of unknown significance (VUS) identified by exome and genome sequencing. Here, we present the results of the CAGI6 Splicing VUS challenge, which invited predictions of the splicing impact of 56 variants ascertained clinically and functionally validated to determine splicing impact. The performance of 12 prediction methods, along with SpliceAI and CADD, was compared on the 56 functionally validated variants. The maximum accuracy achieved was 82% from two different approaches, one weighting SpliceAI scores by minor allele frequency, and one applying the recently published Splicing Prediction Pipeline (SPiP). SPiP performed optimally in terms of sensitivity, while an ensemble method combining multiple prediction tools and information from databases exceeded all others for specificity. Several challenge methods equalled or exceeded the performance of SpliceAI, with ultimate choice of prediction method likely to depend on experimental or clinical aims. One quarter of the variants were incorrectly predicted by at least 50% of the methods, highlighting the need for further improvements to splicing prediction methods for successful clinical application.

Source specific fine particles and rates of asthma and COPD healthcare encounters pre- and post-implementation of the Tier 3 vehicle emissions control regulations - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; Philip K. Hopke; David Q. Rich (Journal of Hazardous Materials, 2025)

Paleoichthyology in the Philippines: A review of Cenozoic fish fossils with insights on its current status and future opportunities - Dominique Mediodia; Abigael Castro; Meyrick Tablizo; David Policarpio; Joeven Calvelo; John Phillip Baguio; Antero Borja; Chien-Hsiang Lin; Allan Gil Fernando (Geobios, 2025)

Improving hepatoprotective effect of naringin against alcohol-induced liver injury by encapsulation in microalgae-derived extracellular vesicles - Jiawen Song; Qianqian Jiao; Lei Zhou; Shengfeng Peng; Suyun Lin; David Julian McClements; Wei Liu (Food Bioscience, 2025)

Microplastics alter crystal growth in coral skeleton structures - Pei-Ying Lin; Shu-Ling Hsieh; De-Sing Ding; Chen-Tung Arthur Chen; David E. Beck; Shuchen Hsieh (Environmental Chemistry Letters, 2025)

Cyclodextrin regulates the binding of quercetin to plasma proteins: Potentially enhancing bioavailability and efficacy - Zhiheng Zhang; Baicun Chen; Qianzhu Lin; Xiaojing Li; Huang Zhang; David Julian McClements; Zhengyu Jin; Chao Qiu (Food Bioscience, 2025)

Recent advances in bio-based co-delivery systems for food bioactive compounds: A review - Zhiheng Zhang; Jilong Wang; Wenbo Miao; Qianzhu Lin; Hangyan Ji; Xiaojing Li; David Julian McClements; Zhengyu Jin; Chao Qiu (Food Bioscience, 2025)

Preparation of emulsion-template oleogels: Tuning properties by controlling initial water content and evaporation method - Wenbo Miao; Zhiheng Zhang; Qianzhu Lin; David Julian McClements; Hangyan Ji; Liming Jiang; Jinsheng Wen; Zhengyu Jin; Chao Qiu (Food Hydrocolloids, 2025)

Toward reproducible and interoperable environmental modeling: Integration of HydroShare with server-side methods for exposing large-extent spatial datasets to models - Young-Don Choi; Iman Maghami; Jonathan L. Goodall; Lawrence Band; Ayman Nassar; Laurence Lin; Linnea Saby; Zhiyu Li; Shaowen Wang; Chris Calloway; Hong Yi; Martin Seul; et al. (Environmental Modelling & Software, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

Composite biopolymer foams fabricated from natural aldehyde functionalized chitosan-whey protein amyloid fibrils: Application for removal of phthalate esters from water - Jilong Wang; Qianzhu Lin; Chao Qiu; David Julian McClements; Hangyan Ji; Zhengyu Jin (Carbohydrate Polymers, 2025)

Ground ozone rise during the 2022 shanghai lockdown caused by the unfavorable emission reduction ratio of nitrogen oxides and volatile organic compounds - Qian Wang; Yuewu Li; Fangqian Zhong; Wanqi Wu; Hongliang Zhang; Rong Wang; Yusen Duan; Qingyan Fu; Qing Li; Lin Wang; Shaocai Yu; Abdewahid Mellouki; et al. (Atmospheric Environment, 2025)

The Jinchang deposit, Ailaoshan Belt: overprint of Miocene orogenic gold mineralization on Triassic hydrothermal nickel sulfide mineralization - Huajian Li; Qingfei Wang; David Groves; Chaoyi Dong; Weijun Weng; Wei Ma; Lin Yang; Ziqing Zhu; Jun Deng (Mineralium Deposita, 2025)

Development and use of DJ-1 affinity microcolumns to screen and study small drug candidates for Parkinson's disease - Jacob C. Jones; Jiusheng Lin; Sadia Sharmeen; Md Masudur Rahman; Ha H. Truong; Ting-Rong Chern; Mark A. Wilson; David S. Hage (Analytica Chimica Acta, 2025)

Prediction of Drug-Drug Interactions for Highly Plasma Protein Bound Compounds - David Tess; Makayla Harrison; Jian Lin; Rui Li; Li Di (The AAPS Journal, 2024)

Challenges to and importance of considering early and intermediate ontogenetic stages in mangrove forest recovery and restoration - Taylor M. Sloey; Sean P. Charles; Lin Xiong; Edward Castañeda-Moya; Erik S. Yando; David Lagomasino (Marine Pollution Bulletin, 2024)

Experimental study of liquid drop impact on granular medium: Drop spreading/splashing and particle ejection - Shangtuo Qian; Han Ye; David Z. Zhu; Junqiang Lin; Ke Hu; Jiangang Feng (Water Research, 2024)

Temperature and carotid intima-medial thickness: The coronary artery risk development in young adults (CARDIA) study - Brian T. Joyce; Jie Yao; Yinan Zheng; Tao Gao; Drew Nannini; Shao Lin; Xin Li; Jaymie Meliker; Qianqian Song; David R. Jacobs; Donald Lloyd-Jones; Lifang Hou; et al. (Science of The Total Environment, 2024)

Sulfur-functionalized rice straw biochar for enhanced cadmium sorption: Spectroscopic, kinetic and computational insights - M.M.M. Ahmed; Chih-Hao Liao; Yu-Ting Liu; S. Venkatesan; Yi-Chen Hsieh; H.M. Nail; Hui-Min David Wang; Ming-Chang Lin; Shih-Hao Jien; Yu-min Tzou (Journal of Cleaner Production, 2024)

Contrasting orbital rhythms preserved in loess grain-size records across the Chinese Loess Plateau - Deai Zhao; Guoqiao Xiao; Chunju Huang; Haibin Wu; Qingzhen Hao; David B. Kemp; Shaohua Tian; Zhipeng Wu; Hao Lu; Gaowen Dai; Shuzhen Peng; Changyan Tang; et al. (Global and Planetary Change, 2024)

Interaction of zein/HP-β-CD nanoparticles with digestive enzymes: Enhancing curcumin bioavailability - Zhiheng Zhang; Wenbo Miao; Hangyan Ji; Qianzhu Lin; Xiaojing Li; Shangyuan Sang; David Julian McClements; Zhengyu Jin; Chao Qiu (Food Chemistry, 2024)

Screening and safety assessment of migrating substances released from biodegradable packaging materials into milk - Chuang-Chuang Zhao; Qin-Bao Lin; Cang-Hao Xie; Yi-Qi Liu; Huai-Ning Zhong; Wei-Yue Gu; David Julian McClements; Da Ma (Food Control, 2024)

Aluminate-activated nano-SiO2 for enhancing water vapor barrier properties in polymers films: A safe and effective strategy - Chuang-Chuang Zhao; Qin-Bao Lin; Yan-Fen Chen; Huai-Ning Zhong; David Julian McClements; Da Ma (Food Packaging and Shelf Life, 2024)

Effects of the organochlorine pesticide metabolite p,p’-DDE on the gastrointestinal lipidome in fish: A novel toxicity pathway for a legacy pollutant - Alexis M. Wormington; David J. Gabrielli; Mohammad-Zaman Nouri; Ashley M. Lin; Sarah E. Robinson; John A. Bowden; Nancy D. Denslow; Tara Sabo-Attwood; Joseph H. Bisesi (Environmental Pollution, 2024)

Impact of fine particulate pollution exposures on respiratory health in a megacity of Pakistan - Qiaoxuan Lin; Ziqiang Lin; Shao Lin; Zafar Fatmi; Nadeem A. Rizvi; Mirza M. Hussain; Azhar Siddique; Omosehin D. Moyebi; David O. Carpenter; Haider A. Khwaja (Atmospheric Pollution Research, 2024)

Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

Energy and fertigation consumption and economic viability of a light blocking film in greenhouse lettuce production - Jing He; Terry Lin; Weiguang Liang; Sachin Chavan; Subbu Sethuvenkatraman; Mark Goldsworthy; David Tissue; Zhong-Hua Chen (Journal of Cleaner Production, 2024)

Sub-national scale mapping of individual olive trees integrating Earth observation and deep learning - Chenxi Lin; Junxiong Zhou; Leikun Yin; Rachid Bouabid; David Mulla; Elinor Benami; Zhenong Jin (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

High water resistance starch based intelligent label for the freshness monitoring of beverages - Yun Wang; David Julian McClements; Zipei Zhang; Ruojie Zhang; Kuang He; Ziqiang Lin; Xinwen Peng; Zhenlin Xu; Man Meng; Hangyan Ji; Jianwei Zhao; Zhengyu Jin; et al. (Food Chemistry, 2024)

PM2.5 and its components and respiratory disease healthcare encounters – Unanticipated increased exposure-response relationships in recent years after environmental policies - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Philip K. Hopke; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; David Q. Rich (Environmental Pollution, 2024)

Natural shading is helpful but not sufficient for mitigating warming in green sea turtle nests in the tropical South China Sea - Tsung-Han Liu; Ming-Shiou Jeng; Chan-Yuan David Lee; Chih-Wei Tu; Po-Hsiung Lin; Chaolun Allen Chen; Chia-Ying Ko (Biological Conservation, 2024)

Impact of cross-reactivity and herd immunity on SARS-CoV-2 pandemic severity - Nana Owusu-Boaitey; Lucas Böttcher; Daihai He; Ryenchindorj Erkhembayar; Lin Yang; Dong-Hyun Kim; Anton Barchuk; David H. Gorski; Jonathan Howard (Infectious Diseases, 2024)

Marine heatwaves alter competition between the cultured macroalga Gracilariopsis lemaneiformis and the harmful bloom alga Skeletonema costatum - Lin Gao; Yonglong Xiong; Fei-Xue Fu; David A. Hutchins; Kunshan Gao; Guang Gao (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Construction of oleogels based on emulsion gels stabilized by glycyrrhizic acid and chitosan - Qianzhu Lin; Chenxi Wang; Zhengyu Jin; Liming Jiang; Jinsheng Wen; David Julian McClements; Chao Qiu (Food Hydrocolloids, 2024)

Recent advances in the application of starch derivatives in baked foods: Effects on quality and functionality - Han Hu; Qianzhu Lin; David Julian McClements; Hangyan Ji; Zhengyu Jin; Chao Qiu (Trends in Food Science & Technology, 2024)

Fabrication and characterization of polydopamine-mediated zein-based nanoparticle for delivery of bioactive molecules - Zhiheng Zhang; Han Jiang; Guo Chen; Wenbo Miao; Qianzhu Lin; Shangyuan Sang; David Julian McClements; Aiquan Jiao; Zhengyu Jin; Jinpeng Wang; Chao Qiu (Food Chemistry, 2024)

Pickering emulsions stabilized by essential oil-tannin-chitosan particles: Microstructure, stability, antibacterial activity, and antioxidant activity - Jingxian Niu; Qianzhu Lin; Xiaojing Li; David Julian McClements; Hangyan Ji; Zhengyu Jin; Chao Qiu (Food Hydrocolloids, 2024)

Plant-based delivery systems for controlled release of hydrophilic and hydrophobic active ingredients: Pea protein-alginate bigel beads - Qianzhu Lin; Xiaojing Li; David Julian McClements; Zhengyu Jin; Chao Qiu; Guanghua Li (Food Hydrocolloids, 2024)

Systemic oxidative stress levels during the course of pregnancy: Associations with exposure to air pollutants - Xiangtian Wang; Yan Lin; Yihui Ge; Emily Craig; Xiaodong Liu; Richard K. Miller; Sally W. Thurston; Jessica Brunner; Emily S. Barrett; Thomas G. O'Connor; David Q. Rich; Junfeng (Jim) Zhang (Environmental Pollution, 2024)

An effective preserving strategy for strawberries by constructing pectin/starch coatings reinforced with functionalized eggshell fillers - Hao Xu; Yihao Huang; Kuang He; Ziqiang Lin; David Julian McClements; Yao Hu; Hao Cheng; Xinwen Peng; Zhengyu Jin; Long Chen (Food Chemistry, 2024)

Enhanced silicate weathering accelerates forest carbon sequestration by stimulating the soil mineral carbon pump - Tongtong Xu; Zuoqiang Yuan; Sara Vicca; Daniel S. Goll; Guochen Li; Luxiang Lin; Hui Chen; Boyuan Bi; Qiong Chen; Chenlu Li; Xing Wang; Chao Wang; et al. (Global Change Biology, 2024)
Enhanced silicate rock weathering (ERW) is an emerging strategy for carbon dioxide removal (CDR) from the atmosphere to mitigate anthropogenic climate change. ERW aims at promoting soil inorganic carbon sequestration by accelerating geochemical weathering processes. Theoretically, ERW may also impact soil organic carbon (SOC), the largest carbon pool in terrestrial ecosystems, but experimental evidence for this is largely lacking. Here, we conducted a 2‐year field experiment in tropical rubber plantations in the southeast of China to evaluate the effects of wollastonite powder additions (0, 0.25, and 0.5 kg m −2 ) on both soil organic and inorganic carbon at 0–10 cm depth. We found that ERW significantly increased the concentration of SOC and HCO 3 − , but the increases in SOC were four and eight times higher than that of HCO 3 − with low‐ and high‐level wollastonite applications. ERW had positive effects on the accrual of organic carbon in mineral‐associated organic matter (MAOM) and macroaggregate fractions, but not on particulate organic matter. Path analysis suggested that ERW increased MAOM mainly by increasing the release of Ca, Si, and Fe, and to a lesser extent by stimulating root growth and microbial‐derived carbon inputs. Our study indicates that ERW with wollastonite can promote SOC sequestration in stable MOAM in surface soils through both the soil mineral carbon pump and microbial carbon pump. These effects may have been larger than the inorganic CDR during our experiment. We argue it is essential to account for the responses of SOC in the assessments of CDR by ERW.

Reconstruction of seamless harmonized Landsat Sentinel-2 (HLS) time series via self-supervised learning - Hao Liu; Hankui K. Zhang; Bo Huang; Lin Yan; Khuong K. Tran; Yuean Qiu; Xiaoyang Zhang; David P. Roy (Remote Sensing of Environment, 2024)

Volatile budgets and gold mobilization in metasomatized sub-continental lithospheric mantle - Yanning Wang; Qingfei Wang; David I. Groves; Shengchao Xue; Tingyi Wang; Lin Yang; Jun Deng (Geochimica et Cosmochimica Acta, 2024)

Review of formation mechanisms and quality regulation of chewiness in staple foods: Rice, noodles, potatoes and bread - Guifang Huang; David Julian McClements; Kuang He; Zipei Zhang; Ziqiang Lin; Zhenlin Xu; Yidong Zou; Zhengyu Jin; Long Chen (Food Research International, 2024)

Urine cadmium and urolithiasis: A systematic review and meta-analysis - Yuan-Hsin Chen; Chih-Fu Wei; Ya-Yun Cheng; Carol Mita; Chinh Lu Duc Hoang; Cheng-Kuan Lin; Yu-Tzu Chang; David C. Christiani (Environmental Research, 2024)

Challenges in assessing and managing multi-hazard risks: A European stakeholders perspective - Robert Šakić Trogrlić; Karina Reiter; Roxana L. Ciurean; Stefania Gottardo; Silvia Torresan; Anne Sophie Daloz; Lin Ma; Noemi Padrón Fumero; Sharon Tatman; Stefan Hochrainer-Stigler; Marleen C. de Ruiter; Julius Schlumberger; et al. (Environmental Science & Policy, 2024)

Nitrogen aerosols in New Delhi, India: Speciation, formation, and sources - Qiaomin Pei; Xin Wan; David Widory; Kirpa Ram; Bhupesh Adhikary; Guangming Wu; Xing Diao; Hemraj Bhattarai; Yan-Lin Zhang; Mark Loewen; Zhiyuan Cong (Atmospheric Research, 2024)

Changes in plasma concentrations of per- and Polyfluoroalkyl substances after bariatric surgery in adolescents from the Teen-Longitudinal Assessment of Bariatric Surgery (Teen-LABS) study - Brittney O. Baumert; Sandrah P. Eckel; Jesse A. Goodrich; Zhenjiang Li; Nikos Stratakis; Douglas I. Walker; Yinqi Zhao; Fabian Christoph Fischer; Scott Bartell; Damaskini Valvi; Xiangping Lin; Zoe Coates Fuentes; et al. (Science of The Total Environment, 2024)

Municipal solid waste management challenges in developing regions: A comprehensive review and future perspectives for Asia and Africa - Zhechen Zhang; Zhonghao Chen; Jiawen Zhang; Yunfei Liu; Lin Chen; Mingyu Yang; Ahmed I. Osman; Mohamed Farghali; Engui Liu; Dalia Hassan; Ikko Ihara; Kun Lu; et al. (Science of The Total Environment, 2024)

Effects on soil carbon storage from municipal biosolids application to agricultural fields - Zheya Lin; G.W. Price; Chang Liang; David L. Burton; Derek H. Lynch (Journal of Environmental Management, 2024)

Abscisic acid treatment prolongs the postharvest life of strawberry fruit by regulating sucrose and cell wall metabolism - Yaoyao Zhao; David A. Brummell; Qiong Lin; Yuquan Duan (Food Bioscience, 2024)

Fabrication and characterization of emulsion-template oleogels assembled from octenyl succinic anhydride starch/chitosan electrostatic complexes - Wenbo Miao; David Julian McClements; Zhiheng Zhang; Qianzhu Lin; Hangyan Ji; Jinpeng Wang; Zhengyu Jin; Guanghua Li; Liming Jiang; Jinsheng Wen; Shangyuan Sang; Chao Qiu (Food Hydrocolloids, 2024)

Recent progress in the hydrophobic modification of starch-based films - Ziqiang Lin; Hao Cheng; Kuang He; David Julian McClements; Zhengyu Jin; Zhenlin Xu; Man Meng; Xinwen Peng; Long Chen (Food Hydrocolloids, 2024)

Encapsulation and protection of β-carotene in Pickering emulsions stabilized by chitosan-phytic acid-cyclodextrin nanoparticles - Qianzhu Lin; Han Jiang; Xiaojing Li; David Julian McClements; Shangyuan Sang; Jinpeng Wang; Aiquan Jiao; Zhengyu Jin; Chao Qiu (Food Bioscience, 2024)

Life cycle assessment and techno-economic analysis of sustainable bioenergy production: a review - Ahmed I. Osman; Bingbing Fang; Yubing Zhang; Yunfei Liu; Jiacheng Yu; Mohamed Farghali; Ahmed K. Rashwan; Zhonghao Chen; Lin Chen; Ikko Ihara; David W. Rooney; Pow-Seng Yap (Environmental Chemistry Letters, 2024)
The global expansion of the bioenergy industry raises concerns, emphasizing the need for careful evaluation and sustainable management. To facilitate this, life cycle assessments beyond greenhouse gas emissions and energy balance are essential, along with the standardization of assessment methodologies to enable meaningful comparisons. Here, we review life cycle assessment, chemical aspects, and policy implication of bioenergy production. We discuss life cycle assessment in terms of concepts, methods, impacts, greenhouse gases, land use, water consumption, bioethanol, biodiesel, biogas, and techno-economic analysis. Chemical aspects comprise reaction processes and means to improve efficiency. Concerning policies, tools, and frameworks that encourage sustainable energy production are presented. We found that carbon dioxide removal ranges from 45 to 99% in various bioenergy processes. The review also emphasizes the importance of chemistry in advancing sustainable bioenergy production for a more sustainable and secure energy future.

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Change in rate of healthcare encounters for respiratory infection from air pollution exposure after improved vehicle emissions standards in New York State - Daniel P. Croft; Mark J. Utell; Han Liu; Shao Lin; Philip K. Hopke; Sally W. Thurston; Yunle Chen; David Q. Rich (Air Quality, Atmosphere & Health, 2024)
The introduction of Tier 3 light-duty vehicles with reduced emissions began in New York State (NYS) in 2017, with required compliance by 2025. We hypothesized that improved air quality during the early implementation of Tier 3 (2017–2019) would result in reduced rates of hospitalizations and emergency department (ED) visits for respiratory infection associated with increased PM 2.5 compared to 2014–2016 (pre-Tier 3). Using data on adult patients hospitalized or having an ED visit for influenza, upper respiratory infection, culture-negative pneumonia, or respiratory bacterial infection, living within 15 miles of six air quality monitoring sites in NY, and a case-crossover design and conditional logistic regression, we estimated the rates of respiratory infection hospitalizations and ED visits associated with increased ambient PM 2.5 concentrations in the previous 0–6 days and each week thereafter up to 1 month. Interquartile range (IQR) increases in PM 2.5 in the previous 6 days were associated with 4.6% (95% CI: − 0.5, 10.1) and 11.9% (95% CI = 6.1, 18.0) increased rates of influenza hospitalizations in 2014–2016 and 2017–2019, respectively. This pattern of larger relative rates in 2017–2019 observed at all lag times was only present in males hospitalized for influenza but not other infections or in females. The rates of respiratory infection visits associated with increased PM 2.5 were generally not reduced in this early Tier 3 implementation period compared to 2014–2016. Limited fleet penetration of Tier 3 vehicles and differences in particle deposition, infection type, and sex by period may all have contributed to this lack of improvement.

Sight and blindness: The relationship between ostracod eyes, water depth, and light availability in the Arctic Ocean - Jingwen Zhang; Moriaki Yasuhara; Chih‐Lin Wei; Skye Yunshu Tian; Kyawt K. T. Aye; Laura Gemery; Thomas M. Cronin; Peter Frenzel; David J. Horne (Limnology and Oceanography, 2024)
Eye loss has been a long‐standing interest in evolutionary biology. Many organisms that inhabit environments without light penetration, for example the deep sea, exhibit eye loss and thus become blind. However, water‐depth distribution of eyes in marine organisms is poorly understood. Ostracods are widely distributed crustaceans, and many sighted marine ostracods have eye tubercles (lenses) on their shells. Since eye tubercles are visible on the shells illustrated in much literature, it is easy to determine their presence or absence via a literature survey. Here, we used a large Arctic‐wide ostracod census dataset (Arctic Ostracode Database) to calculate the eye index (the percentage of species with eyes), and compare them with water depth and light availability. As water depth increases, eye index values decrease and become constantly zero in water deeper than 1000 m. Similar decline of sighted species with increasing depth is also known in isopods and amphipods, suggesting that it may be common in other crustaceans and perhaps in deep‐sea organisms in general. We also show that eye index values increase as light availability increases. This study is the first to quantify how distributions of sighted and blind species change with light availability, giving baseline information on vision in the deep sea.

Tree species, mycorrhizal associations, and land-use history as drivers of cohesion in soil biota communities and microbe-fauna interactions - Petr Heděnec; Hanan Almahasheer; Qiang Lin; Yan Peng; Haifeng Zheng; David Pessanha Siqueira; Kai Yue; Umar Hussaini bin Tarmizi; Mohamad Aqmal-Naser; Siti Norasikin Ismail; Amirah Alias; Johannes Rousk; et al. (Forest Ecology and Management, 2024)

Fabrication of starch-based oleogels using capillary bridges: Potential for application as edible inks in 3D food printing - Wenbo Miao; Yijie Fu; Zhiheng Zhang; Qianzhu Lin; Xiaojing Li; Shangyuan Sang; David Julian McClements; Han Jiang; Hangyan Ji; Chao Qiu; Zhengyu Jin (Food Hydrocolloids, 2024)

Recent advances in the formation and identification of nanoparticle protein coronas and their effects on the digestion and absorption of polyphenols - Zhiheng Zhang; Han Jiang; Wenbo Miao; Qianzhu Lin; Xiaojing Li; Shangyuan Sang; David Julian McClements; Aiquan Jiao; Zhengyu Jin; Chao Qiu (Trends in Food Science & Technology, 2024)

Cross-sectional and prospective associations of early childhood circulating metals with early and mid-childhood cognition in the Project Viva cohort - Ruwan Thilakaratne; Pi-I D. Lin; Sheryl L. Rifas-Shiman; Julio Landero; Robert O. Wright; David Bellinger; Emily Oken; Andres Cardenas (Environmental Research, 2024)

Clinical Investigation of Large Volume Subcutaneous Delivery up to 25 mL for Lean and Non-Lean Subjects - Xiangnan Dang; Han Shih; Rakesh Sharma; Daneen T. Angwin-Kaerner; Kathleen Lin; Shiven Kapur; Nagarajan R. Thyagarajapuram; Galen H. Shi; David S. Collins (Pharmaceutical Research, 2024)

Evaluating the Educational Value of Cancer Registries — a Systematic Review and Thematic Analysis - James Lin; Hugo C. Temperley; Kirsten Larkins; Caitlin Waters; Kit Loong Chong; Jack Maida; David Proud; Adele Burgess; Alexander Heriot; Philip Smart; Helen Mohan (Journal of Cancer Education, 2024)

Biomaterials technology and policies in the building sector: a review - Lin Chen; Yubing Zhang; Zhonghao Chen; Yitong Dong; Yushan Jiang; Jianmin Hua; Yunfei Liu; Ahmed I. Osman; Mohamed Farghali; Lepeng Huang; David W. Rooney; Pow-Seng Yap (Environmental Chemistry Letters, 2024)
Traditional building materials have some drawbacks in the construction industry, particularly in terms of greenhouse gas emissions and energy consumption. Biomaterials derived from renewable sources are a promising alternative, significantly reducing the greenhouse effect and enhancing energy efficiency. However, traditional materials still dominate the construction sector, and there is a lack of understanding among some policymakers and developers regarding biomaterials. Here, we review building biomaterials and their policies and life cycle assessment through case studies. Bio-based materials have the potential to reduce over 320,000 tons of carbon dioxide emissions by 2050. They also exhibit advantages like decreasing water absorption by 40%, reducing energy consumption by 8.7%, enhancing acoustic absorption by 6.7%, and improving mechanical properties. We summarize recent advancements in mycelial materials, bioconcrete, natural fibers, and fiber-reinforced composites. We also explore the contributions of nanotechnology and microalgae technology in enhancing biomaterials' thermal insulation and eco-friendliness.

Benefits and limitations of recycled water systems in the building sector: a review - Lin Chen; Zhonghao Chen; Yunfei Liu; Eric Lichtfouse; Yushan Jiang; Jianmin Hua; Ahmed I. Osman; Mohamed Farghali; Lepeng Huang; Yubing Zhang; David W. Rooney; Pow-Seng Yap (Environmental Chemistry Letters, 2024)
Building construction requires important amounts of freshwater, thus depleting the already stressed natural water resources. This issue could be addressed by using recycled water in construction and in building systems. However, integrating greywater recycling systems is limited by complexity, costs, vulnerability to environmental fluctuations, and coordination of policymakers, developers, and construction practitioners. Here, we review recycled water systems in buildings with focus on case studies of successful implementations, policies, recycled water treatment in buildings, and health aspects. Compared to conventional tap water, the incorporation of recycled water enhances the consistency and workability of reclaimed water concrete by 12–14%, and it increases concrete viscosity by 11% and yield stress by 25%. We discuss the intricacies of building water recycling systems, with emphasizing on conserving water, mitigating environmental impact, and enhancing economic efficiency. Challenges include water quality assurance, dual piping infrastructure, and regulatory compliance. Government interventions, including incentives, mandates, and subsidy policies, emerge as drivers for widespread adoption. Technological advancements, such as membrane filtration and advanced oxidation processes, are examined for strengths and limitations.

Green building practices to integrate renewable energy in the construction sector: a review - Lin Chen; Ying Hu; Ruiyi Wang; Xiang Li; Zhonghao Chen; Jianmin Hua; Ahmed I. Osman; Mohamed Farghali; Lepeng Huang; Jingjing Li; Liang Dong; David W. Rooney; et al. (Environmental Chemistry Letters, 2024)
The building sector is significantly contributing to climate change, pollution, and energy crises, thus requiring a rapid shift to more sustainable construction practices. Here, we review the emerging practices of integrating renewable energies in the construction sector, with a focus on energy types, policies, innovations, and perspectives. The energy sources include solar, wind, geothermal, and biomass fuels. Case studies in Seattle, USA, and Manama, Bahrain, are presented. Perspectives comprise self-sufficiency, microgrids, carbon neutrality, intelligent buildings, cost reduction, energy storage, policy support, and market recognition. Incorporating wind energy into buildings can fulfill about 15% of a building's energy requirements, while solar energy integration can elevate the renewable contribution to 83%. Financial incentives, such as a 30% subsidy for the adoption of renewable technologies, augment the appeal of these innovations.

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Variability in the phytoplankton response to upwelling across an iron limitation mosaic within the California current system - YuanYu Lin; Olivia Torano; Logan Whitehouse; Emily Pierce; Claire P. Till; Matthew Hurst; Robert Freiberger; Travis Mellett; Maria T. Maldonado; Jian Guo; Mariam Sutton; David Zeitz; et al. (Limnology and Oceanography, 2024)
Coastal upwelling currents such as the California Current System (CCS) comprise some of the most productive biological systems on the planet. Diatoms dominate these upwelling events in part due to their rapid response to nutrient entrainment. In this region, they may also be limited by the micronutrient iron (Fe), an important trace element primarily involved in photosynthesis and nitrogen assimilation. The mechanisms behind how diatoms physiologically acclimate to the different stages of the upwelling conveyor belt cycle remain largely uncharacterized. Here, we explore their physiological and metatranscriptomic response to the upwelling cycle with respect to the Fe limitation mosaic that exists in the CCS. Subsurface, natural plankton assemblages that would potentially seed surface blooms were examined over wide and narrow shelf regions. The initial biomass and physiological state of the phytoplankton community had a large impact on the overall response to simulated upwelling. Following on‐deck incubations under varying Fe physiological states, our results suggest that diatoms quickly dominated the blooms by “frontloading” nitrogen assimilation genes prior to upwelling. However, diatoms subjected to induced Fe limitation exhibited reductions in carbon and nitrogen uptake and decreasing biomass accumulation. Simultaneously, they exhibited a distinct gene expression response which included increased expression of Fe‐starvation induced proteins and decreased expression of nitrogen assimilation and photosynthesis genes. These findings may have significant implications for upwelling events in future oceans, where changes in ocean conditions are projected to amplify the gradient of Fe limitation in coastal upwelling regions.

Iron nanoparticle coating and plasma-activated water cleaning as a biofouling removal method for reverse osmosis membranes suitable for desalination - Angelina Egorova; Binbin Xia; Heema Kumari Nilesh Vyas; Maria Magdalena Armendáriz-Ontiveros; Yi-Chen Lin; Alejandra Garcia-Garcia; David K. Wang; Patrick J. Cullen; Gustavo Fimbres Weihs; Anne Mai-Prochnow (Journal of Water Process Engineering, 2024)

Preparation and characterization of zein-based core-shell nanoparticles for encapsulation and delivery of hydrophobic nutrient molecules: Enhancing environmental stress resistance and antioxidant activity - Zhiheng Zhang; Yaxu Meng; Jinpeng Wang; Chao Qiu; Wenbo Miao; Qianzhu Lin; Xiaojing Li; Shangyuan Sang; David Julian McClements; Aiquan Jiao; Zhengyu Jin (Food Hydrocolloids, 2024)

Inherited BRCA1 and RNF43 pathogenic variants in a familial colorectal cancer type X family - James M. Chan; Mark Clendenning; Sharelle Joseland; Peter Georgeson; Khalid Mahmood; Jihoon E. Joo; Romy Walker; Julia Como; Susan Preston; Shuyi Marci Chai; Yen Lin Chu; Aaron L. Meyers; et al. (Familial Cancer, 2024)
Genetic susceptibility to familial colorectal cancer (CRC), including for individuals classified as Familial Colorectal Cancer Type X (FCCTX), remains poorly understood. We describe a multi-generation CRC-affected family segregating pathogenic variants in both BRCA1 , a gene associated with breast and ovarian cancer and RNF43 , a gene associated with Serrated Polyposis Syndrome (SPS). A single family out of 105 families meeting the criteria for FCCTX (Amsterdam I family history criteria with mismatch repair (MMR)-proficient CRCs) recruited to the Australasian Colorectal Cancer Family Registry (ACCFR; 1998–2008) that underwent whole exome sequencing (WES), was selected for further testing. CRC and polyp tissue from four carriers were molecularly characterized including a single CRC that underwent WES to determine tumor mutational signatures and loss of heterozygosity (LOH) events. Ten carriers of a germline pathogenic variant BRCA1 :c.2681_2682delAA p.Lys894ThrfsTer8 and eight carriers of a germline pathogenic variant RNF43 :c.988 C > T p.Arg330Ter were identified in this family. Seven members carried both variants, four of which developed CRC. A single carrier of the RNF43 variant met the 2019 World Health Organization (WHO 2019 ) criteria for SPS, developing a BRAF p.V600 wildtype CRC. Loss of the wildtype allele for both BRCA1 and RNF43 variants was observed in three CRC tumors while a LOH event across chromosome 17q encompassing both genes was observed in a CRC. Tumor mutational signature analysis identified the homologous recombination deficiency (HRD)-associated COSMIC signatures SBS3 and ID6 in a CRC for a carrier of both variants. Our findings show digenic inheritance of pathogenic variants in BRCA1 and RNF43 segregating with CRC in a FCCTX family. LOH and evidence of BRCA1-associated HRD supports the importance of both these tumor suppressor genes in CRC tumorigenesis.

The interactions between olivine dissolution and phytoplankton in seawater: Potential implications for ocean alkalinization - Canru Li; Xiangdong Liu; Yan Li; Yuan Jiang; Xianghui Guo; David A. Hutchins; Jian Ma; Xin Lin; Minhan Dai (Science of The Total Environment, 2024)

Evaluate the effect of β-cyclodextrin on the sensory and physicochemical properties of bitter gourd extract during thermal processing - Cam Thi Hong Tran; Hui-Min David Wang; Le Thi Hong Anh; Chitsan Lin; Chun-Yung Huang; Chia-Hung Kuo (Food Chemistry, 2024)

Editorial: The discovery, identification and application of marine microorganisms derived natural products - Ting Shi; Bo Wang; Dong-Lin Zhao; David J. Newman (Frontiers in Marine Science, 2024)

Effects of field-aging on the impact of biochar on herbicide fate and microbial community structure in the soil environment - Hongguang Cheng; Dan Xing; Gratien Twagirayezu; Shan Lin; Shangyi Gu; Chenglong Tu; Paul W. Hill; David R. Chadwick; Davey L. Jones (Chemosphere, 2024)

Treatment of Lateral Canthal Lines With RelabotulinumtoxinA, an Investigational Liquid Botulinum Toxin: Clinical Efficacy and Safety Results From the READY-2 Phase 3 Trial - Glynis Ablon; David Bank; Theda Kontis; Sherrif F Ibrahim; Melanie Palm; Sue Ellen Cox; Jason K Rivers; Lisa Grunebaum; Mitchel P Goldman; Shannon Humphrey; Xiaoming Lin; Schafiq Nabhani; et al. (Toxicon, 2024)

Comparing thermoregulatory responses between short and long moderate intensity intermittent exercise protocols with the same duty cycle - Tze-Huan Lei; Chien Lin; Tatsuro Amano; Anna Ooue; Toby Mündel; James David Cotter; Naoto Fujii; Takeshi Nishiyasu; Narihiko Kondo (Journal of Thermal Biology, 2024)

The inhibitory mechanism of amylase inhibitors and research progress in nanoparticle-based inhibitors - Qianzhu Lin; Chao Qiu; Xiaojing Li; Shangyuan Sang; David Julian McClements; Long Chen; Jie Long; Aiquan Jiao; Yaoqi Tian; Zhengyu Jin (Critical Reviews in Food Science and Nutrition, 2023)

The relationship between greenspace exposure and telomere length in the National Health and Nutrition Examination Survey - S. Scott Ogletree; Jing-Huei Huang; David Reif; Lin Yang; Christopher Dunstan; Nnamdi Osakwe; Jae In Oh; J. Aaron Hipp (Science of The Total Environment, 2023)

Per- and polyfluoroalkyl substances and organofluorine in lakes and waterways of the northwestern Great Basin and Sierra Nevada - Michael DeNicola; Zunhui Lin; Oscar Quiñones; Brett Vanderford; Mingrui Song; Paul Westerhoff; Eric Dickenson; David Hanigan (Science of The Total Environment, 2023)

Divergent successions increase soil water recharge capacity accompanied by higher evapotranspiration in alpine meadow - Zeng Cui; David Dunkerley; Jingxue Zhao; Gao-Lin Wu (CATENA, 2023)

Electrification of steam cracking as a pathway to reduce the impact of the petrochemical industry on climate change - Oleksii Mynko; Mike Bonheure; Ismaël Amghizar; David J. Brown; Lin Chen; Guy B. Marin; Rodrigo Freitas de Alvarenga; Didem Civancik Uslu; Jo Dewulf; Kevin M. Van Geem (Journal of Cleaner Production, 2023)

Biochar facilitates biofuel production through batch single-stage and two-stage digestion of grass silage and cattle slurry - Xue Ning; Chen Deng; Xihui Kang; Richard O'Shea; David M. Wall; Richen Lin; Jerry D. Murphy (Journal of Cleaner Production, 2023)

Nepalese indoor cookstove smoke extracts alter human airway epithelial gene expression, DNA methylation and hydroxymethylation - Poojitha Rajasekar; Robert J. Hall; K.C. Binaya; Parth S. Mahapatra; Siva P. Puppala; Dhruma Thakker; Julia L. MacIsaac; David Lin; Michael Kobor; Charlotte E. Bolton; Ian Sayers; Ian P. Hall; et al. (Environmental Pollution, 2023)

Advancing co-production for transformative change by synthesizing guidance from case studies on the sustainable management and governance of natural resources - Fernanda A. van Maurik Matuk; Bas Verschuuren; Piero Morseletto; Torsten Krause; David Ludwig; Steven J. Cooke; Moacir Haverroth; Marieke Meesters; Thomas J.M. Mattijssen; Sabine Keßler; Tomaz R. Lanza; Esther Milberg; et al. (Environmental Science & Policy, 2023)

Generating high spatial resolution exposure estimates from sparse regulatory monitoring data - Yihui Ge; Zhenchun Yang; Yan Lin; Philip K. Hopke; Albert A. Presto; Meng Wang; David Q. Rich; Junfeng Zhang (Atmospheric Environment, 2023)

Did Early Pleistocene hominins control hammer strike angles when making stone tools? - Li Li; Jonathan S. Reeves; Sam C. Lin; David R. Braun; Shannon P. McPherron (Journal of Human Evolution, 2023)

Improving biomethane production from biochar-supplemented two-stage anaerobic digestion of on-farm feedstocks - Xue Ning; Chen Deng; Daniel T. Hickey; Anga Hackula; Richard O'Shea; David M. Wall; Richen Lin; Jerry D. Murphy (Journal of Cleaner Production, 2023)

Enterohemorrhagic Escherichia coli O157:H7 antigens produced in transgenic lettuce effective as an oral vaccine in mice - Yun-Lin Su; Mariano Larzábal; Huan Song; Tianfang Cheng; Yufang Wang; Libia Yael Smith; Angel Adrian Cataldi; David W. Ow (Theoretical and Applied Genetics, 2023)

RETRACTED ARTICLE: Artificial intelligence-based solutions for climate change: a review - Lin Chen; Zhonghao Chen; Yubing Zhang; Yunfei Liu; Ahmed I. Osman; Mohamed Farghali; Jianmin Hua; Ahmed Al-Fatesh; Ikko Ihara; David W. Rooney; Pow-Seng Yap (Environmental Chemistry Letters, 2023)
Climate change is a major threat already causing system damage to urban and natural systems, and inducing global economic losses of over $500 billion. These issues may be partly solved by artificial intelligence because artificial intelligence integrates internet resources to make prompt suggestions based on accurate climate change predictions. Here we review recent research and applications of artificial intelligence in mitigating the adverse effects of climate change, with a focus on energy efficiency, carbon sequestration and storage, weather and renewable energy forecasting, grid management, building design, transportation, precision agriculture, industrial processes, reducing deforestation, and resilient cities. We found that enhancing energy efficiency can significantly contribute to reducing the impact of climate change. Smart manufacturing can reduce energy consumption, waste, and carbon emissions by 30–50% and, in particular, can reduce energy consumption in buildings by 30–50%. About 70% of the global natural gas industry utilizes artificial intelligence technologies to enhance the accuracy and reliability of weather forecasts. Combining smart grids with artificial intelligence can optimize the efficiency of power systems, thereby reducing electricity bills by 10–20%. Intelligent transportation systems can reduce carbon dioxide emissions by approximately 60%. Moreover, the management of natural resources and the design of resilient cities through the application of artificial intelligence can further promote sustainability.

BioDeepTime: A database of biodiversity time series for modern and fossil assemblages - Jansen Smith; Marina C. Rillo; Ádám T. Kocsis; Maria Dornelas; David Fastovich; Huai‐Hsuan M. Huang; Lukas Jonkers; Wolfgang Kiessling; Qijian Li; Lee Hsiang Liow; Miranda Margulis‐Ohnuma; Stephen Meyers; et al. (Global Ecology and Biogeography, 2023)
Motivation We have little understanding of how communities respond to varying magnitudes and rates of environmental perturbations across temporal scales. BioDeepTime harmonizes assemblage time series of presence and abundance data to help facilitate investigations of community dynamics across timescales and the response of communities to natural and anthropogenic stressors. BioDeepTime includes time series of terrestrial and aquatic assemblages of varying spatial and temporal grain and extent from the present‐day to millions of years ago. Main Types of Variables Included BioDeepTime currently contains 7,437,847 taxon records from 10,062 assemblage time series, each with a minimum of 10 time steps. Age constraints, sampling method, environment and taxonomic scope are provided for each time series. Spatial Location and Grain The database includes 8752 unique sampling locations from freshwater, marine and terrestrial ecosystems. Spatial grain represented by individual samples varies from quadrats on the order of several cm 2 to grid cells of ~100 km 2 . Time Period and Grain BioDeepTime in aggregate currently spans the last 451 million years, with the 10,062 modern and fossil assemblage time series ranging in extent from years to millions of years. The median extent of modern time series is 18.7 years and for fossil series is 54,872 years. Temporal grain, the time encompassed by individual samples, ranges from days to tens of thousands of years. Major Taxa and Level of Measurement The database contains information on 28,777 unique taxa with 4,769,789 records at the species level and another 271,218 records known to the genus level, including time series of benthic and planktonic foraminifera, coccolithophores, diatoms, ostracods, plants (pollen), radiolarians and other invertebrates and vertebrates. There are to date 7012 modern and 3050 fossil time series in BioDeepTime. Software Format SQLite, Comma‐separated values.

Mapping smallholder cashew plantations to inform sustainable tree crop expansion in Benin - Leikun Yin; Rahul Ghosh; Chenxi Lin; David Hale; Christoph Weigl; James Obarowski; Junxiong Zhou; Jessica Till; Xiaowei Jia; Nanshan You; Troy Mao; Vipin Kumar; et al. (Remote Sensing of Environment, 2023)

Deadlock in transition to a net-zero socially robust knowledge - Kuei-Tien Chou; Mu-Xing Lin; David Walther (Environmental Science & Policy, 2023)

Trends in use of sodium-glucose co-transporter 2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor agonists (GLP-1RA) in Australia in the era of increased evidence of their cardiovascular benefits (2014–2022) - Jialing Lin; Sallie-Anne Pearson; Jerry R. Greenfield; Kyeong Hye Park; Alys Havard; David Brieger; Richard O. Day; Michael O. Falster; Juliana de Oliveira Costa (European Journal of Clinical Pharmacology, 2023)
Purpose To investigate trends in SGLT2i and GLP-1RA use in Australia in the era of increased evidence of their cardiovascular benefits. Methods We used national dispensing claims for a 10% random sample of Australians to estimate the number of prevalent and new users (no dispensing in the prior year) of SGLT2i or GLP-1RA per month from January 2014 to July 2022. We assessed prescriber specialty and prior use of other antidiabetic and cardiovascular medicines as a proxy for evidence of type 2 diabetes (T2D) and cardiovascular conditions, respectively. Results We found a large increase in the number of prevalent users (216-fold for SGLT2i; 11-fold for GLP-1RA); in July 2022 approximately 250,000 Australians were dispensed SGLT2i and 120,000 GLP-1RA. Most new users of SGLT2i or GLP-1RA had evidence of both T2D and cardiovascular conditions, although from 2022 onwards, approximately one in five new users of SGLT2i did not have T2D. The proportion of new users initiating SGLT2i by cardiologists increased after 2021, reaching 10.0% of initiations in July 2022. Among new users with evidence of cardiovascular conditions, empagliflozin was the most commonly prescribed SGLT2i, while dulaglutide or semaglutide was the most common GLP-1RA. Conclusion SGLT2i and GLP-1RA use is increasing in Australia, particularly in populations with higher cardiovascular risk. The increased use of SGLT2i among people without evidence of T2D suggests that best-evidence medicines are adopted in Australia across specialties, aligning with new evidence and expanding indications.

Strategies to save energy in the context of the energy crisis: a review - Mohamed Farghali; Ahmed I. Osman; Israa M. A. Mohamed; Zhonghao Chen; Lin Chen; Ikko Ihara; Pow-Seng Yap; David W. Rooney (Environmental Chemistry Letters, 2023)
New technologies, systems, societal organization and policies for energy saving are urgently needed in the context of accelerated climate change, the Ukraine conflict and the past coronavirus disease 2019 pandemic. For instance, concerns about market and policy responses that could lead to new lock-ins, such as investing in liquefied natural gas infrastructure and using all available fossil fuels to compensate for Russian gas supply cuts, may hinder decarbonization efforts. Here we review energy-saving solutions with a focus on the actual energy crisis, green alternatives to fossil fuel heating, energy saving in buildings and transportation, artificial intelligence for sustainable energy, and implications for the environment and society. Green alternatives include biomass boilers and stoves, hybrid heat pumps, geothermal heating, solar thermal systems, solar photovoltaics systems into electric boilers, compressed natural gas and hydrogen. We also detail case studies in Germany which is planning a 100% renewable energy switch by 2050 and developing the storage of compressed air in China, with emphasis on technical and economic aspects. The global energy consumption in 2020 was 30.01% for the industry, 26.18% for transport, and 22.08% for residential sectors. 10–40% of energy consumption can be reduced using renewable energy sources, passive design strategies, smart grid analytics, energy-efficient building systems, and intelligent energy monitoring. Electric vehicles offer the highest cost-per-kilometer reduction of 75% and the lowest energy loss of 33%, yet battery-related issues, cost, and weight are challenging. 5–30% of energy can be saved using automated and networked vehicles. Artificial intelligence shows a huge potential in energy saving by improving weather forecasting and machine maintenance and enabling connectivity across homes, workplaces, and transportation. For instance, 18.97–42.60% of energy consumption can be reduced in buildings through deep neural networking. In the electricity sector, artificial intelligence can automate power generation, distribution, and transmission operations, balance the grid without human intervention, enable lightning-speed trading and arbitrage decisions at scale, and eliminate the need for manual adjustments by end-users.

Advances in preparation, interaction and stimulus responsiveness of protein-based nanodelivery systems - Qianzhu Lin; Shengju Ge; David Julian McClements; Xiaojing Li; Zhengyu Jin; Aiquan Jiao; Jinpeng Wang; Jie Long; Xueming Xu; Chao Qiu (Critical Reviews in Food Science and Nutrition, 2023)

Occurrences of similar viral diversity in campus wastewater and reclaimed water of a university dormitory - Hsion-Wen David Kuo; Diaiti Zure; Chih-Rong Lin (Chemosphere, 2023)

Identification of Heterotopic Mineralization and Adjacent Pathology in the Equine Fetlock Region by Low-Field Magnetic Resonance Imaging, Cone-Beam and Fan-Beam Computed Tomography - Szu-Ting Lin; Vanessa G. Peter; Stefano Schiavo; Rachel Pokora; Hayley Patrick; Nick Bolas; Alastair K. Foote; David R. Sargan; Rachel C. Murray (Journal of Equine Veterinary Science, 2023)

Physicochemical stability, antioxidant activity, and antimicrobial activity of quercetin-loaded zein nanoparticles coated with dextrin-modified anionic polysaccharides - Zhiheng Zhang; Yao Hu; Hangyan Ji; Qianzhu Lin; Xiaojing Li; Shangyuan Sang; David Julian McClements; Long Chen; Jie Long; Aiquan Jiao; Xueming Xu; Zhengyu Jin; et al. (Food Chemistry, 2023)

Contribution from ancient subducted slab to the Emeishan Large Igneous Province: Constraints from the petrogenesis of mafic intrusions in the western Guangxi area, South China - Hao Lin; Xiangke Wu; Hongfeng Qin; Changming Li; Yukun Li; Huimin Su; David A. Holwell; Dongyang Zhang (Lithos, 2023)

Can urban polycentricity improve air quality? Evidence from Chinese cities - Will W. Qiang; Haowen Luo; Yuxuan Xiao; David W.H. Wong; Alex S. Shi; Ziwei Lin; Bo Huang; Harry F. Lee (Journal of Cleaner Production, 2023)

Green construction for low-carbon cities: a review - Lin Chen; Lepeng Huang; Jianmin Hua; Zhonghao Chen; Lilong Wei; Ahmed I. Osman; Samer Fawzy; David W. Rooney; Liang Dong; Pow-Seng Yap (Environmental Chemistry Letters, 2023)
The construction industry is a major user of non-renewable energy and contributor to emission of greenhouse gases, thus requiring to achieve net-zero carbon emissions by 2050. Indeed, construction activities account for 36% of global energy consumption and 39% of global carbon dioxide emissions. Reducing carbon emissions requires adapted government policies, carbon emission analysis and calculation models, and sustainable materials. Here, we review green construction with focus on history, carbon emissions, policies, models, life cycle assessment, and sustainable materials such as biochar, bioplastic, agricultural waste, animal wool, fly ash and self-healing concrete. Analysis of carbon emissions over the building life cycle shows that the construction phase accounts for 20–50% of total carbon emissions. The average ratio of construction phase annual emissions to operation phase emissions is 0.62. We present national policy frameworks and technology roadmaps from the United States of America, Japan, China, and the European Union, highlighting plans to achieve carbon neutrality in the building sector.

Solubility controls on plutonium and americium release in subsurface environments exposed to acidic processing wastes - Hilary P. Emerson; Sergey I. Sinkov; Carolyn I. Pearce; Kirk J. Cantrell; Calvin H. Delegard; Michelle M.V. Snyder; May-Lin Thomas; Dallas D. Reilly; Edgar C. Buck; Lucas E. Sweet; Amanda J. Casella; Jennifer C. Carter; et al. (Applied Geochemistry, 2023)

Measuring riverine macroplastic: Methods, harmonisation, and quality control - Rachel Hurley; Hans Fredrik Veiteberg Braaten; Luca Nizzetto; Eirik Hovland Steindal; Yan Lin; François Clayer; Tim van Emmerik; Nina Tuscano Buenaventura; David Petersen Eidsvoll; Asle Økelsrud; Magnus Norling; Hans Nicolai Adam; et al. (Water Research, 2023)

Prolonged Mesozoic intracontinental gold mineralization in the South China Block controlled by lithosphere architecture and evolving Paleo-Pacific Plate subduction - Yushan Zeng; Qingfei Wang; David I. Groves; M. Santosh; Yanning Wang; Tingyi Wang; Lin Yang; Wei Chen; Jun Deng (Earth-Science Reviews, 2023)

Corrigendum to “Carbonate U Pb and illite Rb Sr geochronology of sediment-hosted gold: A case study of Yata gold deposit” [Chemical Geology 621 (2023) 121352] - Ruixue Wang; Qingfei Wang; Jian-Xin Zhao; David I. Groves; Christopher L. Kirkland; Yue-Xing Feng; I. Tonguç Uysal; Lin Yang; Jun Deng (Chemical Geology, 2023)

Identification of genetic loci associated with five agronomic traits in alfalfa using multi-environment trials - Sen Lin; Cesar A. Medina; Guojie Wang; David Combs; Glenn Shewmaker; Steve Fransen; Don Llewellyn; Steven Norberg; Long-Xi Yu (Theoretical and Applied Genetics, 2023)

Planetary cross-linked structure design of hybrid organosilica membrane by amine-driven polymerization for CO2 separation - Jing-Yi Li; Yu-Ting Lin; David K. Wang; Hui-Hsin Tseng; Ming-Yen Wey (Journal of Cleaner Production, 2023)

Three-dimensional full-loop numerical simulation of coal and sludge co-combustion in a circulating fluidized bed - Wanqiang Wu; Lunbo Duan; Yuanqiang Duan; Lin Li; Daoyin Liu; David Pallarès (Fuel, 2023)

Peanut protein-polysaccharide hydrogels based on semi-interpenetrating networks used for 3D/4D printing - Qianzhu Lin; Yao Hu; Chao Qiu; Xiaojing Li; Shangyuan Sang; David Julian McClements; Long Chen; Jie Long; Xueming Xu; Jinpeng Wang; Zhengyu Jin (Food Hydrocolloids, 2023)

Yam Seep at Four-Way Closure Ridge: a prominent active gas seep system at the accretionary wedge SW offshore Taiwan - Yiting Tseng; Miriam Römer; Saulwood Lin; Thomas Pape; Christian Berndt; Tzu-Ting Chen; Charles K. Paull; David W. Caress; Gerhard Bohrmann (International Journal of Earth Sciences, 2023)
Hydroacoustic surveys at the accretionary wedge southwest of Taiwan reveal a confined active hydrocarbon seepage area of ~ 49,000 m 2 in ~ 1350 m water depth on the northern crest of the Four-Way Closure Ridge, which we call Yam Seep. In this study, multibeam and side-scan sonar data acquired during surveys with an autonomous underwater vehicle during an expedition with R/V Ocean Researcher I in 2017 showed that the area is characterized by rough topography and high seafloor backscatter. Seafloor observations with a video sled and sediment sampling with gravity corers and the MeBo seafloor drill rig during an expedition with R/V SONNE in 2018 revealed that the area is almost entirely covered by intensely fractured methane-derived carbonates, which indicate that seepage has been ongoing for thousands of years. Hydroacoustic anomalies (‘flares’) in the water column indicated the presence of several gas bubble emission sites mostly at the center and eastern flank of the area in 2019. Drilling through massive carbonates in the northwestern part of Yam Seep induced free gas escape from a depth of ~ 5.1 m. This suggests the presence of gas hydrates in the subsurface as the seep area is located well within the gas hydrate stability zone. The inter-disciplinary investigations of the Yam Seep demonstrate that upward migration of light hydrocarbons and seafloor discharge has a considerable influence on the seabed properties.

Cost, environmental impact, and resilience of renewable energy under a changing climate: a review - Ahmed I. Osman; Lin Chen; Mingyu Yang; Goodluck Msigwa; Mohamed Farghali; Samer Fawzy; David W. Rooney; Pow-Seng Yap (Environmental Chemistry Letters, 2023)
Energy derived from fossil fuels contributes significantly to global climate change, accounting for more than 75% of global greenhouse gas emissions and approximately 90% of all carbon dioxide emissions. Alternative energy from renewable sources must be utilized to decarbonize the energy sector. However, the adverse effects of climate change, such as increasing temperatures, extreme winds, rising sea levels, and decreased precipitation, may impact renewable energies. Here we review renewable energies with a focus on costs, the impact of climate on renewable energies, the impact of renewable energies on the environment, economy, and on decarbonization in different countries. We focus on solar, wind, biomass, hydropower, and geothermal energy. We observe that the price of solar photovoltaic energy has declined from $0.417 in 2010 to $0.048/kilowatt-hour in 2021. Similarly, prices have declined by 68% for onshore wind, 60% for offshore wind, 68% for concentrated solar power, and 14% for biomass energy. Wind energy and hydropower production could decrease by as much as 40% in some regions due to climate change, whereas solar energy appears the least impacted energy source. Climate change can also modify biomass productivity, growth, chemical composition, and soil microbial communities. Hydroelectric power plants are the most damaging to the environment; and solar photovoltaics must be carefully installed to reduce their impact. Wind turbines and biomass power plants have a minimal environmental impact; therefore, they should be implemented extensively. Renewable energy sources could decarbonize 90% of the electricity industry by 2050, drastically reducing carbon emissions, and contributing to climate change mitigation. By establishing the zero carbon emission decarbonization concept, the future of renewable energy is promising, with the potential to replace fossil fuel-derived energy and limit global temperature rise to 1.5 °C by 2050.

Centenarian clocks: epigenetic clocks for validating claims of exceptional longevity - Eric Dec; James Clement; Kaiyang Cheng; George M. Church; Michael B. Fossel; David H. Rehkopf; Luis Rosero-Bixby; Michael S. Kobor; David TS. Lin; Ake T. Lu; Zhe Fei; Wei Guo; et al. (GeroScience, 2023)
Claims surrounding exceptional longevity are sometimes disputed or dismissed for lack of credible evidence. Here, we present three DNA methylation-based age estimators (epigenetic clocks) for verifying age claims of centenarians. The three centenarian clocks were developed based on n = 7039 blood and saliva samples from individuals older than 40, including n = 184 samples from centenarians, 122 samples from semi-supercentenarians (aged 105 +), and 25 samples from supercentenarians (aged 110 +). The oldest individual was 115 years old. Our most accurate centenarian clock resulted from applying a neural network model to a training set composed of individuals older than 40. An epigenome-wide association study of age in different age groups revealed that age effects in young individuals (age < 40) are correlated ( r = 0.55) with age effects in old individuals (age > 90). We present a chromatin state analysis of age effects in centenarians. The centenarian clocks are expected to be useful for validating claims surrounding exceptional old age.

Long-term exposure to particulate matter and COPD mortality: Insights from causal inference methods based on a large population cohort in southern China - Ying Wang; Zhicheng Du; Yuqin Zhang; Shirui Chen; Shao Lin; Philip K. Hopke; David Q. Rich; Kai Zhang; Xiaobo X. Romeiko; Xinlei Deng; Yanji Qu; Yu Liu; et al. (Science of The Total Environment, 2023)

Carbonate U Pb and illite Rb Sr geochronology of sediment-hosted gold: A case study of Yata gold deposit - Ruixue Wang; Qingfei Wang; Jian-Xin Zhao; David I. Groves; Christopher L. Kirkland; Yue-Xing Feng; I. Tonguç Uysal; Lin Yang; Jun Deng (Chemical Geology, 2023)

Evaluation of drought tolerance in sugarcane genotypes using the membership function value of drought tolerance (MFVD) - Chaohua Xu; Jun Mao; Xujuan Li; David M. Burner; Chunjia Li; Shareif H. Hussin Hussin; Xiuqin Lin; Hongbo Liu; Peifang Zhao; Xin Lu; Xinlong Liu (Euphytica, 2023)

Food values drive Chinese consumers' demand for meat and milk substitutes - Jiayu Sun; David L. Ortega; Wen Lin (Appetite, 2023)

Extraction and characterization of pectic polysaccharides from Choerospondias axillaris peels: Comparison of hot water and ultrasound-assisted extraction methods - Chao Wang; Jing Li; Yi Cao; Jialu Huang; Hongyi Lin; Tiantian Zhao; Lu Liu; Peiyi Shen; David Julian McClements; Jun Chen; Chengmei Liu; Jiyan Liu; et al. (Food Chemistry, 2023)

Bioaccessibility and bioavailability of phytochemicals: Influencing factors, improvements, and evaluations - Yao Hu; Qianzhu Lin; Hui Zhao; Xiaojing Li; Shangyuan Sang; David Julian McClements; Jie Long; Zhengyu Jin; Jinpeng Wang; Chao Qiu (Food Hydrocolloids, 2023)

Circular economy strategies for combating climate change and other environmental issues - Mingyu Yang; Lin Chen; Jiangjiang Wang; Goodluck Msigwa; Ahmed I. Osman; Samer Fawzy; David W. Rooney; Pow-Seng Yap (Environmental Chemistry Letters, 2023)
Global industrialization and excessive dependence on nonrenewable energy sources have led to an increase in solid waste and climate change, calling for strategies to implement a circular economy in all sectors to reduce carbon emissions by 45% by 2030, and to achieve carbon neutrality by 2050. Here we review circular economy strategies with focus on waste management, climate change, energy, air and water quality, land use, industry, food production, life cycle assessment, and cost-effective routes. We observed that increasing the use of bio-based materials is a challenge in terms of land use and land cover. Carbon removal technologies are actually prohibitively expensive, ranging from 100 to 1200 dollars per ton of carbon dioxide. Politically, only few companies worldwide have set climate change goals. While circular economy strategies can be implemented in various sectors such as industry, waste, energy, buildings, and transportation, life cycle assessment is required to optimize new systems. Overall, we provide a theoretical foundation for a sustainable industrial, agricultural, and commercial future by constructing cost-effective routes to a circular economy.

Evaluation of Copper Levels in Dental Calculus of OSF Patients with Chewing Dried Areca-Nut Quids in Hunan Province of Mainland China - Xi-Fan He; Hui Wang; Ye Tian; Te Zhang; Zhi-Peng Qiu; Xiao-Jiao Cui; Jing-Sha Zhou; Xin-Lan Yan; Yi-Wei Wu; Yi-Sha Pan; Yang-Bo Ning; Lin Chen; et al. (Biological Trace Element Research, 2023)

Pollen in the Baltic Sea as viewed from space - Chuanmin Hu; Lin Qi; David C. English; Menghua Wang; Karlis Mikelsons; Brian B. Barnes; Magdalena M. Pawlik; Dariusz Ficek (Remote Sensing of Environment, 2023)

Constant-temperature predictions underestimate growth of a fungal amphibian pathogen under individual host thermal profiles - Sasha E. Greenspan; Elizabeth A. Roznik; Lexie Edwards; Richard Duffy; Lee Berger; Deborah S. Bower; David A. Pike; Lin Schwarzkopf; Ross A. Alford (Journal of Thermal Biology, 2023)

Learning from arid and urban aquatic ecosystems to inform more sustainable and resilient futures - Lauren McPhillips; Marta Berbés-Blázquez; Rebecca Hale; Tamara K. Harms; Vanya Bisht; Liliana Caughman; Sandra M. Clinton; Elizabeth Cook; Xiaoli Dong; Jennifer Edmonds; Sarah Gergel; Rosa Gómez; et al. (Journal of Hydrology, 2023)

Tourmaline chemistry, boron, and strontium isotope systematics trace multiple melt–fluid–rock interaction stages in deeply subducted continental crust - Xin Chen; Shaoyong Jiang; Martin R.Palmer; Hans-Peter Schertl; Aitor Cambeses; David Hernández-Uribe; Kuidong Zhao; Chenggui Lin; Youye Zheng (Geochimica et Cosmochimica Acta, 2023)

Enhancement of lycopene bioaccessibility in tomatoes using excipient emulsions: Effect of dark tea polysaccharides - Chao Wang; Yinxin Fu; Yi Cao; Jialu Huang; Hongyi Lin; Peiyi Shen; David Julian McClements; Lingyu Han; Tiantian Zhao; Xiaoxuan Yan; Qian Li (Food Research International, 2023)

Tree species traits and mycorrhizal association shape soil microbial communities via litter quality and species mediated soil properties - Petr Heděnec; Haifeng Zheng; David Pessanha Siqueira; Qiang Lin; Yan Peng; Inger Kappel Schmidt; Tobias Guldberg Frøslev; Rasmus Kjøller; Johannes Rousk; Lars Vesterdal (Forest Ecology and Management, 2023)

Molecular weight, chain length distribution and long-term retrogradation of cassava starch modified by amylomaltase - Hua-Tsung Lin; An-I Yeh; Tuan-Hua David Ho; Min-Hsiung Pan; Shih Hsin Chen (Food Hydrocolloids, 2023)

Improving probiotic (Lactobacillus casei) viability by encapsulation in alginate-based microgels: Impact of polymeric and colloidal fillers - Qian Li; Hongyi Lin; Jing Li; Lu Liu; Jialu Huang; Yi Cao; Tiantian Zhao; David Julian McClements; Jun Chen; Chengmei Liu; Jiyan Liu; Peiyi Shen; et al. (Food Hydrocolloids, 2023)

Triggering of ST-elevation myocardial infarction by ultrafine particles in New York: Changes following Tier 3 vehicle introduction - Catherine S. Yount; Mark J. Utell; Philip K. Hopke; Sally W. Thurston; Shao Lin; Frederick S. Ling; Yunle Chen; David Chalupa; Xinlei Deng; David Q. Rich (Environmental Research, 2023)

Associations between DNA methylation and genotoxicity among lead-exposed workers in China - Tuanwei Wang; Yu Meng; Yuting Tu; Guanghui Zhang; Kan Wang; Shiyang Gong; Yunxia Zhang; Tongshuai Wang; Anqi Li; David C. Christiani; William Au; Zhao-lin Xia (Environmental Pollution, 2023)

Cover Image - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)

Exogenous polyunsaturated fatty acids ( PUFAs ) influence permeability, antimicrobial peptide resistance, biofilm formation and membrane phospholipid structure in an A‐layer and non‐A ‐layer strain of Aeromonas salmonicida - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)
Aeromonas salmonicida is a Gram‐negative bacterium that can infect a wide host range of fish populations, including salmonids and non‐salmonids as well as freshwater and marine life. Some strains of A. salmonicida cause the disease furunculosis, which can cause lethargy, intestinal inflammation, ulcers, haemorrhaging and death. The infection is spread through fish‐to‐fish contact, and the presence of infection can have devastating effects on cultivated fish populations. The purpose of this study was to explore the ability of non‐A‐layer and A‐layer A. salmonicida strains to incorporate polyunsaturated fatty acids (PUFAs) into their lipid profile and test the phenotypic effects thereof. Lipids were extracted from PUFA‐exposed cultures and analysed for lipid modification by thin‐layer chromatography and ultraperformance liquid chromatography‐mass spectrometry, showing A. salmonicida , regardless of A‐layer, capable of incorporating all seven of the PUFAs studied. Phenotypic effects were determined through the use of assays that tested for biofilm formation, membrane permeability and cyclic peptide susceptibility. Temperature‐dependent effects on biofilm formation were observed, and PUFA exposure showed significant ( p

Mapping of surface-generated noise coherence - Najeem Shajahan; David R Barclay; Ying-Tsong Lin (Frontiers in Marine Science, 2022)
The performance of a hydrophone array can be evaluated by its coherent gain, which depends on the spatial correlation of both the signal of interest and the background noise between different array elements, where one hopes to maximize the former while minimizing the latter with array signal processing. In this paper, a computational vertical noise coherence map of the first zero-crossing is generated near Alvin Canyon, south of Martha’s Vineyard, Massachusetts, to study its dependence on the spatial variation in bathymetry, water column sound speed and sediment type. A two and three-dimensional Parabolic Equation propagation model based on reciprocity theory were used for the simulation. The results showed that the seabed parameters have the greatest impact on vertical noise coherence at the array location in the Alvin Canyon area, when compared to 3-D bathymetric and water column sound speed profile variability, especially in the shallower water. The analysis reveals the ideal spacing for a vertical hydrophone array for better signal detection in acoustic experiments. In the continental shelf and slope regions, the ideal spacing lies between 3λ⁄8 in deep water and λ⁄2 in shallow water, and for areas with strong bathymetric variations the ideal spacing can be determined by comprehensive numerical models.

Dancing to a different tune: changing reproductive seasonality in an introduced chital deer population - Catherine L. Kelly; Lin Schwarzkopf; Iain J. Gordon; Anthony Pople; David L. Kelly; Ben T. Hirsch (Oecologia, 2022)
Male and female reproductive behaviour is typically synchronised. In species such as those in the family Cervidae , reproductive timing is often cued by photoperiod, although in females, it can be dependent on body condition. When a species is introduced to a novel environment, the environment changes, or responses of the sexes to such cues differ, asynchronous reproductive behaviour between males and females may occur. We investigated the seasonality of reproductive behaviour in introduced chital deer in northern Queensland by examining male antler phase in relation to female conception rates. We then analysed the influence of different variables likely to affect the timing of male and female reproductive physiology. The lowest percentage of chital in hard antler in any 1 month in this study was 35% (Fig. 1), but the average value was closer to 50%, thus there was a seasonal peak in antler phase linked with photoperiod. Females conceived at any time of year, but were strongly influenced by the amount of rainfall 3 months prior to conception. This resulted in varying conception peaks year-to-year that often did not correspond to the male’s peak in hard antler. In this system, a proportion of males and females were physiologically and behaviourally ready to mate at any time of the year. We predict that differences in the timing of the peaks between the males and females will lead to increased reproductive skew (variation in reproductive success among individual males). This pattern may select for different mating strategies or physiological mechanisms to increase reproductive success.

Metagenomic next-generation sequencing restores the diagnosis of a rare infectious complication of B cell depletion - Margaux Garzaro; Lin-Pierre Zhao; Nathalie De Castro; Séverine Mercier-Delarue; Francois Camelena; Sabine Pereyre; Marie Gardette; Béatrice Berçot; Marion Malphettes; Cécile Bébéar; Jean-David Bouaziz; Jérôme Le Goff; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Methods to control harmful algal blooms: a review - Barathan Balaji-Prasath; Ying Wang; Yu Ping Su; David P. Hamilton; Hong Lin; Luwei Zheng; Yong Zhang (Environmental Chemistry Letters, 2022)

A Numerical Study of Long-Return Period Near-Bottom Ocean Currents in Lower Cook Inlet, Alaska - David B. Fissel; Yuehua Lin (Journal of Marine Science and Engineering, 2022)
Lower Cook Inlet (LCI) is an important waterway with very large tides and high marine productivity. Oceanographic forcing in LCI is complex due to a combination of tides, seasonal winds, and large freshwater discharges, as well as inflow from the Alaska Coastal Current. From an analysis of historical current meter data sets, deeper ocean currents of LCI were found to have large differences resulting from the dominance of large tides in the northeast portion of LCI while subtidal contributions to the deeper currents are more important relative to the reduced tidal currents in central and western parts of LCI. To compute the largest values of the near-bottom currents of LCI, a 3D hydrodynamical model was developed over a large model domain extending over the full 300 km length of Cook Inlet as well as a large portion of the adjoining Alaska continental shelf region. At the open model boundaries, nine major tidal height constituents were specified based on National Oceanic and Atmospheric Administration (NOAA) tidal gauge data. The model was forced by the spatially varying winds and freshwater discharges for the six gauged rivers in Cook Inlet. The model was verified using available current meter data in the study area. Model runs were carried out for 21 case studies to derive the near-bottom currents for return periods of 1, 10, and 100 years. Within LCI, the extremal values for near bottom currents arise from quite different forcing regimes. Tidal currents are completely dominant in the northeast portion of LCI while for central and western portions, remote wind forcing over the Alaskan continental shelf current, which generates the Alaska Coastal Current, becomes more important.

Spatial patterns and driving factors of carbon stocks in mangrove forests on Hainan Island, China - Yuchen Meng; Ruikun Gou; Jiankun Bai; David Moreno‐Mateos; Charles C. Davis; Luoma Wan; Shanshan Song; Hongsheng Zhang; Xiaoshan Zhu; Guanghui Lin (Global Ecology and Biogeography, 2022)
Aim Mangrove forests are important coastal wetlands for the blue carbon budget and play a significant role in mitigating global climate change. However, spatial patterns of carbon stocks in mangrove forests on an island scale have not been quantified owing to methodological limitations and lack of understanding of controlling factors. We took the entire Hainan Island as a case study and aimed to carry out a comprehensive investigation of the spatial patterns and driving factors of carbon stocks in mangrove forests. Location Southern China. Time period 2017–2020. Major taxa studied Mangrove forest. Methods The upscaling method combined with field surveys and Sentinel‐2 imagery analysis were used to compare different models for optimization of mangrove ecosystem carbon stock estimations. We also used structural equation modelling (SEM) to evaluate the factors driving the distributional patterns of mangrove carbon stocks on an island scale. Results The current total mangrove carbon stock of the entire Hainan Island was estimated to be 703,181 Mg C (with a mean density of 192 Mg C/ha), with the above‐ and below‐ground carbon stocks averaging at 44.7 and 147.3 Mg C/ha, respectively. The mangrove carbon storage in the north‐eastern region of the island was the highest and in the west region the lowest. Sediment nitrogen content and plant species diversity had the most positive driving effects on the distribution of total carbon stock for Hainan Island mangroves. Main conclusions The combination of field surveys and Sentinel‐2 imagery analysis can be applied to regional‐scale estimations of carbon stocks for mangrove forests. Spatial pattens of mangrove carbon stocks vary among locations on Hainan Island, and soil nutrient (especially nitrogen) availability is the dominant factor regulating carbon stock variations along the land‐to‐sea gradient. Our findings have significant implications for better understanding the distribution of mangrove carbon stocks and quantification of the global blue carbon budget.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Tisch Cancer Institute Scholars Program: Mentored Cancer Research Training Pipeline for Medical Students - Kaitlyn Ben-David; Jenny J. Lin; James L. M. Ferrara; Janice L. Gabrilove (Journal of Cancer Education, 2022)

Anodal transcutaneous DC stimulation enhances learning of dynamic balance control during walking in humans with spinal cord injury - Jui-Te Lin; Chao-Jung Hsu; Weena Dee; David Chen; W. Zev Rymer; Ming Wu (Experimental Brain Research, 2022)

Strategies to achieve a carbon neutral society: a review - Lin Chen; Goodluck Msigwa; Mingyu Yang; Ahmed I. Osman; Samer Fawzy; David W. Rooney; Pow-Seng Yap (Environmental Chemistry Letters, 2022)
The increasing global industrialization and over-exploitation of fossil fuels has induced the release of greenhouse gases, leading to an increase in global temperature and causing environmental issues. There is therefore an urgent necessity to reach net-zero carbon emissions. Only 4.5% of countries have achieved carbon neutrality, and most countries are still planning to do so by 2050–2070. Moreover, synergies between different countries have hampered synergies between adaptation and mitigation policies, as well as their co-benefits. Here, we present a strategy to reach a carbon neutral economy by examining the outcome goals of the 26th summit of the United Nations Climate Change Conference of the Parties (COP 26). Methods have been designed for mapping carbon emissions, such as input–output models, spatial systems, geographic information system maps, light detection and ranging techniques, and logarithmic mean divisia. We present decarbonization technologies and initiatives, and negative emissions technologies, and we discuss carbon trading and carbon tax. We propose plans for carbon neutrality such as shifting away from fossil fuels toward renewable energy, and the development of low-carbon technologies, low-carbon agriculture, changing dietary habits and increasing the value of food and agricultural waste. Developing resilient buildings and cities, introducing decentralized energy systems, and the electrification of the transportation sector is also necessary. We also review the life cycle analysis of carbon neutral systems.

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

HIV, pathology and epigenetic age acceleration in different human tissues - Steve Horvath; David T. S. Lin; Michael S. Kobor; Joseph A. Zoller; Jonathan W. Said; Susan Morgello; Elyse Singer; William H. Yong; Beth D. Jamieson; Andrew J. Levine (GeroScience, 2022)
Epigenetic clocks based on patterns of DNA methylation have great importance in understanding aging and disease; however, there are basic questions to be resolved in their application. It remains unknown whether epigenetic age acceleration (EAA) within an individual shows strong correlation between different primary tissue sites, the extent to which tissue pathology and clinical illness correlate with EAA in the target organ, and if EAA variability across tissues differs according to sex. Considering the outsized role of age-related illness in Human Immunodeficiency Virus-1 (HIV), these questions were pursued in a sample enriched for tissue from HIV-infected individuals. We used a custom methylation array to generate DNA methylation data from 661 samples representing 11 human tissues (adipose, blood, bone marrow, heart, kidney, liver, lung, lymph node, muscle, spleen and pituitary gland) from 133 clinically characterized, deceased individuals, including 75 infected with HIV. We developed a multimorbidity index based on the clinical disease history. Epigenetic age was moderately correlated across tissues. Blood had the greatest number and degree of correlation, most notably with spleen and bone marrow. However, blood did not correlate with epigenetic age of liver. EAA in liver was weakly correlated with EAA in kidney, adipose, lung and bone marrow. Clinically, hypertension was associated with EAA in several tissues, consistent with the multiorgan impacts of this illness. HIV infection was associated with positive age acceleration in kidney and spleen. Male sex was associated with increased epigenetic acceleration in several tissues. Preliminary evidence indicates that amyotrophic lateral sclerosis is associated with positive EAA in muscle tissue. Finally, greater multimorbidity was associated with greater EAA across all tissues. Blood alone will often fail to detect EAA in other tissues. While hypertension is associated with increased EAA in several tissues, many pathologies are associated with organ-specific age acceleration.

Correction to: R-praziquantel integrated population pharmacokinetics in preschool- and school-aged African children infected with Schistosoma mansoni and S. haematobium and Lao adults infected with Opisthorchis viverrini - Christine Falcoz; Serge Guzy; Jana Kovač; Isabel Meister; Jean Coulibaly; Somphou Sayasone; David Wesche; Yu-Wei Lin; Jennifer Keiser (Journal of Pharmacokinetics and Pharmacodynamics, 2022)

R-praziquantel integrated population pharmacokinetics in preschool- and school-aged African children infected with Schistosoma mansoni and S. haematobium and Lao adults infected with Opisthorchis viverrini - Christine Falcoz; Serge Guzy; Jana Kovač; Isabel Meister; Jean Coulibaly; Somphou Sayasone; David Wesche; Yu-Wei Lin; Jennifer Keiser (Journal of Pharmacokinetics and Pharmacodynamics, 2022)

Effects of short-term decomposition on isotope values of fish tissues under natural conditions - Kathryn S. Peiman; Hsien-Yung Lin; Michael Power; Scott G. Hinch; David A. Patterson; Steven J. Cooke (Aquatic Ecology, 2022)

The impact of air pollution on COVID-19 pandemic varied within different cities in South America using different models - Haining Huang; Congtian Lin; Xiaobo Liu; Liting Zhu; Ricardo David Avellán-Llaguno; Mauricio Manuel Llaguno Lazo; Xiaoyan Ai; Qiansheng Huang (Environmental Science and Pollution Research, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Comparative Pharmacokinetics and Tissue Concentrations of Flunixin Meglumine and Meloxicam in Tilapia (Oreochromis spp.) - Miriam Martin; Stephen Smith; Michael Kleinhenz; Geraldine Magnin; Zhoumeng Lin; David Kuhn; Shawnee Montgomery; Johann Coetzee (Fishes, 2021)
Evidence of pain perception in fish is well established, but analgesic use in aquaculture is limited. The objective was to investigate the comparative pharmacokinetics of flunixin administered intramuscularly (IM) and meloxicam administered IM or orally (PO) in tilapia. Two hundred and seventy fish were assigned to 1 of 3 treatment groups: flunixin meglumine IM (2.2 mg/kg); meloxicam IM (1 mg/kg); or meloxicam PO (1 mg/kg). Blood and tissue samples were collected from 6 fish per treatment at 14 time points for 10 days. Drug concentrations were determined using ultra-high-pressure liquid chromatography coupled with mass spectroscopy. Plasma concentration versus time data were analyzed with a non-compartmental approach using a commercially available software. Flunixin reached a mean maximum concentration (Cmax) of 4826.7 ng/mL at 0.5 h, had a terminal half-life (T1/2) of 7.34 h, and an area under the concentration–time curve extrapolated to infinity (AUCINF_obs) of 25,261.62 h·ng/mL. Meloxicam IM had a T1/2 of 9.4 h after reaching a Cmax of 11.3 ng/mL at 2 h, with an AUCINF_obs of 150.31 h·ng/mL. Meloxicam PO had a T1/2 of 1.9 h after reaching a Cmax of 72.2 ng/mL at 2 h, with an AUCINF_obs of 400.83 h·ng/mL. Tissue concentrations of both drugs were undetectable by 9 h. Flunixin reached a sufficient plasma concentration to potentially have an analgesic effect, while meloxicam, when administered at the given dosage, likely would not.

Group Size of Indo-Pacific Humpback Dolphins (Sousa chinensis): An Examination of Methodological and Biogeographical Variances - Mingming Liu; Mingli Lin; Xiaoming Tang; Lijun Dong; Peijun Zhang; David Lusseau; Songhai Li (Frontiers in Marine Science, 2021)
Observer-based counts and photo-identification are two well-established methods with an extensive use in cetacean studies. Using these two methods, group size has been widely reported, especially for small dolphins. Both methods may come with potential errors in estimating the group size, yet there is still a lack of comparison between both methods over a broad range of group size. Particularly, biogeographical variances in group size estimates were often mixed with methodological variances, making it difficult to compare estimates from different geographic regions. Here, group size estimates of a small, shallow-water, and near-shore delphinid species, Indo-Pacific humpback dolphins ( Sousa chinensis ), were simultaneously sampled using observer-based counts and photo-identification at three regions in the northern South China Sea. Data showed that dolphin group size from two methods were highly variable and associated with sampling regions. Generalized linear mixed models (GLMMs) indicated that dolphin group size significantly differed among regions. Statistical examinations further demonstrated dolphin group size could be affected by a complex combination of methodological and biogeographical variances. A common hurdle to examine potential factors influencing the estimation process is the inability to know the true group size at each sample. Therefore, other methods that could generate comparable estimates to represent true group size are warranted in future studies. To conclude, our findings present a better understanding of methodological and biogeographical variances in group size estimates of humpback dolphins, and help yield more robust abundance and density estimation for these vulnerable animals.

Safety and tolerability of chronic intranasal oxytocin in older men: results from a randomized controlled trial - Jillian M. Rung; Marilyn Horta; Erin M. Tammi; Eliany Perez; Marite C. Ojeda; Tian Lin; Griffin Harris; Jessie Somerville; Dinia Salmeron; Susan E. Beltz; Bhanuprasad Sandesara; David Feifel; et al. (Psychopharmacology, 2021)

Effects of process factors on the performance of electrochemical disinfection for wastewater in a continuous-flow cell reactor - Che-Jen Lin; Ruolin Zhang; Scott A. Waisner; Tabish Nawaz; Lori Center; David B. Gent; Jared L. Johnson; Sabin Holland (Environmental Science and Pollution Research, 2021)

Intra-Population Variability in Group Size of Indo-Pacific Humpback Dolphins (Sousa chinensis) - Mingming Liu; Mingli Lin; David Lusseau; Songhai Li (Frontiers in Marine Science, 2021)
Group size is a key social trait influencing population dynamics of group-living animals. The Indo-Pacific humpback dolphins (IPHDs), Sousa chinensis , a shallow water delphinid species, display a fission-fusion social system. Yet little is known about how social organization of this species vary with temporal scales and behavioral state. In this study, we sampled group size estimates from the world’s second largest population of humpback dolphins ( Sousa spp.), which inhabit the eastern waters of Zhanjiang, China. IPHD group sizes changed seasonally and inter-annually, but not with tidal phases. Group sizes also changed with behavioral state of IPHD groups and with number of mother-calf pairs present. IPHDs formed larger groups in the autumn than in other seasons, which might be related to seasonal changes in food availability and reproductive cycle. Of the groups observed, we recorded the presence of mother-calf pair in 85 groups (i.e., nursery groups: 47 ones with one pair, 25 ones with two pairs, and others with three pairs). Notably, nursery groups were about 2–4 times larger than non-nursery groups. In addition, group sizes greatly increased with the number of mother-calf pairs. Living in relatively large groups, more protection, food, and resources might be available for IPHD mothers and calves, and such social strategy provide higher reproduction efficiency and survival success for this species. During our observations, feeding (45.5%) and traveling (25.2%) represented the majority of IPHD’s behavioral budget, while socializing (8.4%) and resting/milling (6.8%) were not frequently observed. Resting/milling groups were approximately 50% smaller than feeding, traveling, or socializing groups, while the latter three types had a similar mean group size. Large groups when IPHDs foraged, traveled, or socialized, might provide more added group benefits. For the first time, our findings clearly revealed intra-population variability in IPHD group sizes across different behavioral and temporal variables, and provided a better understanding of IPHDs’ adaptations to various biological processes and ecological constraints.

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

Performance of permeable pavement systems on stormwater permeability and pollutant removal - Zhiji Yu; Huihui Gan; Ming Xiao; Biao Huang; David Z. Zhu; Zheyun Zhang; Huanyan Wang; Yongliang Lin; Yonglong Hou; Shuai Peng; Wei Zhang (Environmental Science and Pollution Research, 2021)

From zero to infinity: Minimum to maximum diversity of the planet by spatio‐parametric Rao’s quadratic entropy - Duccio Rocchini; Matteo Marcantonio; Daniele Da Re; Giovanni Bacaro; Enrico Feoli; Giles M. Foody; Reinhard Furrer; Ryan J. Harrigan; David Kleijn; Martina Iannacito; Jonathan Lenoir; Meixi Lin; et al. (Global Ecology and Biogeography, 2021)
Aim The majority of work done to gather information on the Earth's biodiversity has been carried out using in‐situ data, with known issues related to epistemology (e.g., species determination and taxonomy), spatial uncertainty, logistics (time and costs), among others. An alternative way to gather information about spatial ecosystem variability is the use of satellite remote sensing. It works as a powerful tool for attaining rapid and standardized information. Several metrics used to calculate remotely sensed diversity of ecosystems are based on Shannon’s information theory, namely on the differences in relative abundance of pixel reflectances in a certain area. Additional metrics like the Rao’s quadratic entropy allow the use of spectral distance beside abundance, but they are point descriptors of diversity, that is they can account only for a part of the whole diversity continuum. The aim of this paper is thus to generalize the Rao’s quadratic entropy by proposing its parameterization for the first time. Innovation The parametric Rao’s quadratic entropy, coded in R, (a) allows the representation of the whole continuum of potential diversity indices in one formula, and (b) starting from the Rao’s quadratic entropy, allows the explicit use of distances among pixel reflectance values, together with relative abundances. Main conclusions The proposed unifying measure is an integration between abundance‐ and distance‐based algorithms to map the continuum of diversity given a satellite image at any spatial scale. Being part of the rasterdiv R package, the proposed method is expected to ensure high robustness and reproducibility.

Root age influences failure location in grass species during mechanical testing - David Boldrin; Anthony Glyn Bengough; Zijian Lin; Kenneth Wilhelmus Loades (Plant and Soil, 2021)
Aims Root tensile tests are often rejected if failure location is outside the middle section of samples. This study aims to identify where and why failure occurs along a root axis, and hence to revisit current approaches to test-validity. Methods Roots from Festuca arundinacea; Lolium multiflorum; Lolium perenne were sampled from field-grown plants. Roots were tensile tested using a universal testing machine. Root samples were randomly allocated into two groups for testing. Group 1 roots were orientated with the older tissue closest to the top clamp, group 2 roots were orientated oppositely. Tensile strength, Young’s modulus and failure location were recorded for each sample. Results Lolium multiflorum roots were thinner and stronger than roots of Festuca arundinacea. Failure location in tensile tests depended significantly on tissue age with 75% of samples failing in the younger third of root tissue regardless of the root orientation in the testing frame. Only 7% of roots failed in the middle third of the sample. Conclusions Fibrous roots tested in tension were observed to consistently fail in the younger tissue along the root axis. Exclusion of samples which fail outside the middle region of the root axis needs re-evaluation for a range of species.

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

The clinical utility of proton magnetic resonance spectroscopy in traumatic brain injury: recommendations from the ENIGMA MRS working group - Brenda L Bartnik-Olson; Jeffry R Alger; Talin Babikian; Ashley D Harris; Barbara Holshouser; Ivan I Kirov; Andrew A Maudsley; Paul M Thompson; Emily L Dennis; David F Tate; Elisabeth A Wilde; Alexander Lin (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Tracing the origins of recent Queensland fruit fly incursions into South Australia, Tasmania and New Zealand - Ángel-David Popa-Báez; Siu Fai Lee; Heng Lin Yeap; Guy Westmore; Peter Crisp; Dongmei Li; Renee Catullo; Emilie C. Cameron; Owain R. Edwards; Phillip W. Taylor; John G. Oakeshott (Biological Invasions, 2021)

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

Atrial fibrillation rhythm is associated with marked changes in metabolic and myofibrillar protein expression in left atrial appendage - Julie H. Rennison; Ling Li; Cheryl R. Lin; Beth S. Lovano; Laurie Castel; Sojin Youn Wass; Catherine C. Cantlay; Meghan McHale; A. Marc Gillinov; Reena Mehra; Belinda B. Willard; Jonathan D. Smith; et al. (Pflügers Archiv - European Journal of Physiology, 2021)

Application of a Diffusion Charger to Quantify Real-Time Particle Emissions from Light-Duty Vehicles: a Comparison Study with a Particle Size Spectrometer - Heejung Jung; David Quiros; Yang Li; Shaohua Hu; Yue Lin (Emission Control Science and Technology, 2021)

Warming Iron-Limited Oceans Enhance Nitrogen Fixation and Drive Biogeographic Specialization of the Globally Important Cyanobacterium Crocosphaera - Nina Yang; Carlin A. Merkel; Yu-An Lin; Naomi M. Levine; Nicholas J. Hawco; Hai-Bo Jiang; Ping-Ping Qu; Michelle A. DeMers; Eric A. Webb; Fei-Xue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
Primary productivity in the nutrient-poor subtropical ocean gyres depends on new nitrogen inputs from nitrogen fixers that convert inert dinitrogen gas into bioavailable forms. Temperature and iron (Fe) availability constrain marine nitrogen fixation, and both are changing due to anthropogenic ocean warming. We examined the physiological responses of the globally important marine nitrogen fixer, Crocosphaera watsonii across its full thermal range as a function of iron availability. At the lower end of its thermal range, from 22 to 27°C, Crocosphaera growth, nitrogen fixation, and Nitrogen-specific Iron Use Efficiencies (N-IUEs, mol N fixed hour –1 mol Fe –1 ) increased with temperature. At an optimal growth temperature of 27°C, N-IUEs were 66% higher under iron-limited conditions than iron-replete conditions, indicating that low-iron availability increases metabolic efficiency. However, Crocosphaera growth and function decrease from 27 to 32°C, temperatures that are predicted for an increasing fraction of tropical oceans in the future. Altogether, this suggests that Crocosphaera are well adapted to iron-limited, warm waters, within prescribed limits. A model incorporating these results under the IPCC RCP 8.5 warming scenario predicts that Crocosphaera N-IUEs could increase by a net 47% by 2100, particularly in higher-latitude waters. These results contrast with published responses of another dominant nitrogen fixer ( Trichodesmium ), with predicted N-IUEs that increase most in low-latitude, tropical waters. These models project that differing responses of Crocosphaera and Trichodesmium N-IUEs to future warming of iron-limited oceans could enhance their current contributions to global marine nitrogen fixation with rates increasing by ∼91 and ∼22%, respectively, thereby shifting their relative importance to marine new production and also intensifying their regional divergence. Thus, interactive temperature and iron effects may profoundly transform existing paradigms of nitrogen biogeochemistry and primary productivity in open ocean regimes.

Time‐varying trends in frost indicators in the U.S. Southern Great Plains - Yongjun Zhang; Prasanna Gowda; David Brown; Charles Rice; Zachary Zambreski; Seth Kutikoff; Xiaomao Lin (International Journal of Climatology, 2021)
Climatic frost indicators, including the dates of the last spring frost (LSF), the dates of the first fall frost (FFF), and the length of the frost‐free season (FFSL), are critical factors in anthropogenic and natural ecosystem management and can be directly calculated from daily minimum temperatures. Daily minimum temperature from the Applied Climate Information System was used to determine long‐term trends of frost indicators across the U.S. Southern Great Plains. The results demonstrated statistically significant trends of earlier LSF in eastern Kansas, western and eastern Oklahoma, and eastern Texas from 1950 to 2017. However, significantly later FFF trends and longer FFSL trends were mainly identified in eastern Oklahoma and eastern Texas. Overall, the region was characterized by the trends toward earlier LSF, later FFF, and longer FFSL from 1950 to 2017. In addition, the choice of time period in the climatic time series played an important role in LSF, FFF, and FFSL trends. Furthermore, the results from the correlation analysis of LSF and FFF with multiple climate indices indicated that the increasing trends in the spring Arctic Oscillation (AO) were consistent with the earlier onset of spring in Kansas and Texas, and the fall Atlantic Multidecadal Oscillation (AMO) was positively correlated with the later FFF dates in Kansas.

Fine-scale roadkill risk models: understanding the intersection of wildlife and roads - Kristina Chyn; Te-En Lin; David P. Wilkinson; James L. Tracy; A. Michelle Lawing; Lee A. Fitzgerald (Biodiversity and Conservation, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

Whole-brain R1 predicts manganese exposure and biological effects in welders - David A. Edmondson; Chien-Lin Yeh; Sébastien Hélie; Ulrike Dydak (Archives of Toxicology, 2020)

Climate change considerations are fundamental to management of deep‐sea resource extraction - Lisa A. Levin; Chih‐Lin Wei; Daniel C. Dunn; Diva J. Amon; Oliver S. Ashford; William W. L. Cheung; Ana Colaço; Carlos Dominguez‐Carrió; Elva G. Escobar; Harriet R. Harden‐Davies; Jeffrey C. Drazen; Khaira Ismail; et al. (Global Change Biology, 2020)
Climate change manifestation in the ocean, through warming, oxygen loss, increasing acidification, and changing particulate organic carbon flux (one metric of altered food supply), is projected to affect most deep‐ocean ecosystems concomitantly with increasing direct human disturbance. Climate drivers will alter deep‐sea biodiversity and associated ecosystem services, and may interact with disturbance from resource extraction activities or even climate geoengineering. We suggest that to ensure the effective management of increasing use of the deep ocean (e.g., for bottom fishing, oil and gas extraction, and deep‐seabed mining), environmental management and developing regulations must consider climate change. Strategic planning, impact assessment and monitoring, spatial management, application of the precautionary approach, and full‐cost accounting of extraction activities should embrace climate consciousness. Coupled climate and biological modeling approaches applied in the water and on the seafloor can help accomplish this goal. For example, Earth‐System Model projections of climate‐change parameters at the seafloor reveal heterogeneity in projected climate hazard and time of emergence (beyond natural variability) in regions targeted for deep‐seabed mining. Models that combine climate‐induced changes in ocean circulation with particle tracking predict altered transport of early life stages (larvae) under climate change. Habitat suitability models can help assess the consequences of altered larval dispersal, predict climate refugia, and identify vulnerable regions for multiple species under climate change. Engaging the deep observing community can support the necessary data provisioning to mainstream climate into the development of environmental management plans. To illustrate this approach, we focus on deep‐seabed mining and the International Seabed Authority, whose mandates include regulation of all mineral‐related activities in international waters and protecting the marine environment from the harmful effects of mining. However, achieving deep‐ocean sustainability under the UN Sustainable Development Goals will require integration of climate consideration across all policy sectors.

Evolution of the Miocene Ailaoshan orogenic gold deposits, southeastern Tibet, during a complex tectonic history of lithosphere-crust interaction - Qingfei Wang; David I. Groves; Jun Deng; Huajian Li; Lin Yang; Chaoyi Dong (Mineralium Deposita, 2020)

An integrated biophysical approach to discovering mechanisms of NDM-1 inhibition for several thiol-containing drugs - Sarah Fullington; Zishuo Cheng; Caitlyn Thomas; Callie Miller; Kundi Yang; Lin-Cheng Ju; Alexander Bergstrom; Ben A. Shurina; Stacey Lowery Bretz; Richard C. Page; David L. Tierney; Michael W. Crowder (JBIC Journal of Biological Inorganic Chemistry, 2020)

Metabolomics profiling of visceral and abdominal subcutaneous adipose tissue in colorectal cancer patients: results from the ColoCare study - Jennifer Ose; Andreana N. Holowatyj; Johanna Nattenmüller; Biljana Gigic; Tengda Lin; Caroline Himbert; Nina Habermann; David Achaintre; Augustin Scalbert; Pekka Keski-Rahkonen; Jürgen Böhm; Petra Schrotz-King; et al. (Cancer Causes & Control, 2020)

Pyrolysis of fatty acids derived from hydrolysis of brown grease with biosolids - Mehdi Omidghane; Mattia Bartoli; Justice Asomaning; Lin Xia; Michael Chae; David C. Bressler (Environmental Science and Pollution Research, 2020)
The escalating generation of biosolids and increasing regulations regarding their safe handling and disposal have created a great environmental challenge. Recently, biosolids have been incorporated into the hydrolysis step of a two-step thermal lipid conversion process to act as water replacement in the production of renewable chemicals and fuels. Here, the hexane extract recovered from hydrolysis of biosolids, lipids from brown grease hydrolyzed using either water (control) or biosolids as a water replacement, was pyrolyzed at 410–450 °C for 2 h. The product distribution and composition were not significantly different when biosolids were used to hydrolyze brown grease instead of water. The liquid product consisted mainly of alkanes, alkenes, aromatics, and cyclic compounds similar to those in petroleum-derived liquid fuels. However, the use of biosolids as a water substitute resulted in a significant increase in sulphur content of the pyrolysate, which will necessitate processes to reduce the sulphur content before or after pyrolysis. Nevertheless, the pathways proposed in this paper are considered as potentially economically viable approaches to not only resolve the issues associated with disposal of biosolids but also to produce renewable hydrocarbons for fuel and chemical applications.

An Engineered Biomimetic MPER Peptide Vaccine Induces Weakly HIV Neutralizing Antibodies in Mice - Shuai Shao; Wei-Chiao Huang; Cuiyan Lin; Mark D. Hicar; Celia C. LaBranche; David C. Montefiori; Jonathan F. Lovell (Annals of Biomedical Engineering, 2020)

Non-Invasive Quantification of Ventricular Contractility, Arterial Elastic Function and Ventriculo-Arterial Coupling from a Single Diagnostic Encounter Using Simultaneous Arterial Tonometry and Magnetic Resonance Imaging - Mayooran Namasivayam; Audrey Adji; Linda Lin; Christopher S. Hayward; Michael P. Feneley; Michael F. O’Rourke; David W. M. Muller; Andrew Jabbour (Cardiovascular Engineering and Technology, 2020)

Varied movement errors drive learning of dynamic balance control during walking in people with incomplete spinal cord injury: a pilot study - Jui-Te Lin; Chao-Jung Hsu; Weena Dee; David Chen; W. Zev Rymer; Ming Wu (Experimental Brain Research, 2020)

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Inflammation-related genes are associated with epigenetic aging in HIV - Erin E. Sundermann; Mariam A. Hussain; David J. Moore; Steven Horvath; David T. S. Lin; Michael S. Kobor; Andrew Levine (Journal of NeuroVirology, 2019)

The Contributions of Individual Muscle–Tendon Units to the Plantarflexor Group Force–Length Properties - Mehrdad Javidi; Craig P. McGowan; David C. Lin (Annals of Biomedical Engineering, 2019)

Leaf area–length allometry and its implications in leaf shape evolution - Peijian Shi; Mengdi Liu; David A. Ratkowsky; Johan Gielis; Jialu Su; Xiaojing Yu; Ping Wang; Lifang Zhang; Zhiyi Lin; Julian Schrader (Trees, 2019)

Environment‐ and trait‐mediated scaling of tree occupancy in forests worldwide - Haibao Ren; Petr Keil; Xiangcheng Mi; Keping Ma; Zhanqing Hao; Wanhui Ye; Luxiang Lin; Renato Valencia; Christine Dawn Fletcher; Duncan W. Thomas; Robert W. Howe; James Lutz; et al. (Global Ecology and Biogeography, 2019)
Aim The relationship between the proportion of sites occupied by a species and the area of a site [occupancy–area relationship (OAR)] offers key information for biodiversity management and has long fascinated ecologists. We quantified the variation in OAR for 3,157 woody species in 17 forest plots worldwide and tested the relative importance of environment and species traits for explaining this variation and evaluated overall model predictive ability. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We used mixed‐effect regression to examine the observed shape of the OAR (its “slope”) against species‐specific and plot‐wide predictors: coarse‐grain occupancy, tree size, plot species richness, energy availability and topographic complexity. Results We found large variation in OAR slopes, and the variation was strongest among species within plots. The OAR slopes showed a latitudinal trend and were steeper near the equator. As predicted, coarse‐grain occupancy and tree size negatively affected OAR slopes, whereas species richness had a positive effect and explained most of the variance between plots. Although hypothesized directionalities were broadly confirmed, traits and environment had relatively limited overall predictive power. Main conclusions These results document the variation of the OAR for 3,157 species at near‐global extent. We found a latitudinal gradient in OAR slopes and confirmed key hypothesized predictors. But at this global extent and over the large set of species analysed, the remaining unexplained variation in OAR slopes was substantial. Nevertheless, this large‐scale empirical analysis of the OAR offers an initial step towards a more general use of OARs for the fine‐scale prediction of species distributions and abundance.

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Staphylococcal driveline infections are the predominant type of left ventricular assist device associated infections in Singapore - Yii Ean Teh; Choon Pin Lim; Louis Loon Yee Teo; Jia Lin Soon; Victor Tar Toong Chao; Chia Lee Neo; Joycelyn Li Li Tan; Ka Lee Kerk; David Kheng Leng Sim; Teing Ee Tan; Ban Hock Tan; Sivathasan Cumaraswamy; et al. (Infectious Diseases, 2019)

Primary Productivity Dynamics in the Summer Arctic Ocean Confirms Broad Regulation of the Electron Requirement for Carbon Fixation by Light-Phytoplankton Community Interaction - Yuanli Zhu; David J. Suggett; Chenggang Liu; Jianfeng He; Longshan Lin; Fengfeng Le; Joji Ishizaka; Joaquim Goes; Qiang Hao (Frontiers in Marine Science, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Dissolution Testing in Drug Product Development: Workshop Summary Report - Andreas Abend; David Curran; Jesse Kuiper; Xujin Lu; Hanlin Li; Andre Hermans; Pramod Kotwal; Dorys A. Diaz; Michael J. Cohen; Limin Zhang; Erika Stippler; German Drazer; et al. (The AAPS Journal, 2019)

A differential k-mer analysis pipeline for comparing RNA-Seq transcriptome and meta-transcriptome datasets without a reference - Chon-Kit Kenneth Chan; Nedeljka Rosic; Michał T. Lorenc; Paul Visendi; Meng Lin; Paulina Kaniewska; Brett J. Ferguson; Peter M. Gresshoff; Jacqueline Batley; David Edwards (Functional & Integrative Genomics, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Understanding the Impacts of Surface Compositions on the In-Vitro Dissolution and Aerosolization of Co-Spray-Dried Composite Powder Formulations for Inhalation - Sharad Mangal; Rongkun Xu; Heejun Park; Dmitry Zemlyanov; Nivedita Shetty; Yu-Wei Lin; David Morton; Hak-Kim Chan; Jian Li; Qi Tony Zhou (Pharmaceutical Research, 2019)

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey - Piotr Majka; Marcello G. P. Rosa; Shi Bai; Jonathan M. Chan; Bing-Xing Huo; Natalia Jermakow; Meng K. Lin; Yeonsook S. Takahashi; Ianina H. Wolkowicz; Katrina H. Worthy; Ramesh Rajan; David H. Reser; et al. (Brain Structure and Function, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Effect of Subject-Specific Vertebral Position and Head and Neck Size on Calculation of Spine Musculoskeletal Moments - Anita N. Vasavada; Ellis Hughes; Derek D. Nevins; Steven M. Monda; David C. Lin (Annals of Biomedical Engineering, 2018)

Baroclinic Effect on Modeling Deep Flow in Brown Passage, BC, Canada - Yuehua Lin; David B. Fissel; Todd Mudge; Keath Borg (Journal of Marine Science and Engineering, 2018)
Brown Passage is a deep (up to 200 m) ocean channel connecting the western offshore waters of Hecate Strait and Dixon Entrance on the Pacific continental shelf with the eastern inland waters of Chatham Sound in Northern British Columbia, Canada. A high-resolution 3D finite difference hydrodynamic model, COastal CIRculation and SEDiment transport Model (COCIRM-SED), was developed in 2010 and 2013 to determine the tidal and wind-driven currents of this area. The barotropic model results for ocean currents were found to be in reasonably good agreement with the historical ocean current observations at near-surface and middle depth available for Brown Passage. Operated from October 2014 to April 2015, the first modern oceanographic measurement program in Brown Passage found surprisingly strong near-bottom currents (the 99th percentile current speed reaches 53 cm/s at 196 m). As a result, the COCIRM-SED model was modified and rerun, with the most important change incorporating water density/salinity fields as modeled variables. This change led to considerable improvements in the ability of the model to generate episodes of relatively strong currents in the bottom layers. The bottom intensification in ocean currents in Brown Passage is shown to be due to semi-diurnal internal tides, which were not previously included in the barotropic version of the 3D model. This finding for the near-bottom flow from the qualitative modeling study is important for applications of the potential sediment deposition and resuspension studies.

Gross primary productivity of a large metropolitan region in midsummer using high spatial resolution satellite imagery - David L. Miller; Dar A. Roberts; Keith C. Clarke; Yang Lin; Olaf Menzer; Emily B. Peters; Joseph P. McFadden (Urban Ecosystems, 2018)

Black race and distant recurrence after neoadjuvant or adjuvant chemotherapy in breast cancer - Jessica M. Pastoriza; George S. Karagiannis; Juan Lin; Sonali Lanjewar; David Entenberg; John S. Condeelis; Joseph A. Sparano; Xiaonan Xue; Thomas E. Rohan; Maja H. Oktay (Clinical & Experimental Metastasis, 2018)

Modeling the Transport and Fate of Sediments Released from Marine Construction Projects in the Coastal Waters of British Columbia, Canada - David B. Fissel; Yuehua Lin (Journal of Marine Science and Engineering, 2018)
Major marine construction projects, resulting in the release of sediments, are subject to environmental assessment and other regulatory approval processes. An important tool used for this is the development of specialized numerical methods for these marine activities. An integrated set of numerical methods addresses four distinct topics: (1) The near-field release and mixing of suspended sediments into the water column (i.e., the initial dilution zone); (2) the transport of the suspended sediments under the influence of complex ocean currents in the far-field; (3) the settling of the transported suspended sediments onto the seabed; and (4) the potential for resuspension of the deposited sediments due to sporadic occurrences of unusually large near-bottom currents. A review of projects subjected to environmental assessment in the coastal waters of British Columbia, from the year 2006 to 2017, is presented to illustrate the numerical models being used and their ongoing development. Improvements include higher resolution model grids to better represent the near-field, the depiction of particle size dependent vertical settling rates and the computation of resuspension of initially deposited sediments, especially in relation to temporary subsea piles of sediments arising from trenching for marine pipelines. The ongoing challenges for this numerical modeling application area are also identified.

Before and after: craving, mood, and background stress in the hours surrounding drug use and stressful events in patients with opioid-use disorder - Kenzie L. Preston; William J. Kowalczyk; Karran A. Phillips; Michelle L. Jobes; Massoud Vahabzadeh; Jia-Ling Lin; Mustapha Mezghanni; David H. Epstein (Psychopharmacology, 2018)

Behavioural responses of an Australian colubrid snake (Dendrelaphis punctulatus) to a novel toxic prey item (the Cane Toad Rhinella marina) - John Llewelyn; Neil C. Choyce; Benjamin L. Phillips; Jonathan K. Webb; David J. Pearson; Lin Schwarzkopf; Richard Shine (Biological Invasions, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Linking muscle metabolism and functional variation to field swimming performance in bluegill sunfish (Lepomis macrochirus) - David J. Ellerby; Shauna Cyr; Angela X. Han; Mika Lin; Lloyd A. Trueblood (Journal of Comparative Physiology B, 2018)

Evidence that NF-κB and MAPK Signaling Promotes NLRP Inflammasome Activation in Neurons Following Ischemic Stroke - David Yang-Wei Fann; Yun-An Lim; Yi-Lin Cheng; Ker-Zhing Lok; Prasad Chunduri; Sang-Ha Baik; Grant R. Drummond; S. Thameem Dheen; Christopher G. Sobey; Dong-Gyu Jo; Christopher Li-Hsian Chen; Thiruma V. Arumugam (Molecular Neurobiology, 2018)

Yangonindimers A-C, three new kavalactone dimers from Piper methysticum (kava) - Jia-Ling Song; Bai-Lin Li; Yao Yuan; Ling-Hui Nie; Jia Niu; David Chiu; Zhi-Fang Xu; Jie-Wei Wu; Sheng-Xiang Qiu (Natural Product Research, 2017)

Approaches for Establishing Clinically Relevant Dissolution Specifications for Immediate Release Solid Oral Dosage Forms - Andre Hermans; Andreas M. Abend; Filippos Kesisoglou; Talia Flanagan; Michael J. Cohen; Dorys A. Diaz; Y. Mao; Limin Zhang; Gregory K. Webster; Yiqing Lin; David A. Hahn; Carrie A. Coutant; et al. (The AAPS Journal, 2017)

Context and craving during stressful events in the daily lives of drug-dependent patients - Kenzie L. Preston; William J. Kowalczyk; Karran A. Phillips; Michelle L. Jobes; Massoud Vahabzadeh; Jia-Ling Lin; Mustapha Mezghanni; David H. Epstein (Psychopharmacology, 2017)

regSNPs-splicing: a tool for prioritizing synonymous single-nucleotide substitution - Xinjun Zhang; Meng Li; Hai Lin; Xi Rao; Weixing Feng; Yuedong Yang; Matthew Mort; David N. Cooper; Yue Wang; Yadong Wang; Clark Wells; Yaoqi Zhou; et al. (Human Genetics, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Effects of resource addition on recovery of production and plant functional composition in degraded semiarid grasslands - Qing Chen; David U. Hooper; Hui Li; Xiao Ying Gong; Fei Peng; Hong Wang; Klaus Dittert; Shan Lin (Oecologia, 2017)

Congenic mapping identifies a novel Idd9 subregion regulating type 1 diabetes in NOD mice - Bixuan Lin; Ashley E. Ciecko; Erin MacKinney; David V. Serreze; Yi-Guang Chen (Immunogenetics, 2017)

Glycerol enhances fungal germination at the water‐activity limit for life - Andrew Stevenson; Philip G. Hamill; Ángel Medina; Gerhard Kminek; John D. Rummel; Jan Dijksterhuis; David J. Timson; Naresh Magan; Su‐Lin L. Leong; John E. Hallsworth (Environmental Microbiology, 2017)
Summary For the most‐extreme fungal xerophiles, metabolic activity and cell division typically halts between 0.700 and 0.640 water activity (approximately 70.0–64.0% relative humidity). Here, we investigate whether glycerol can enhance xerophile germination under acute water‐activity regimes, using an experimental system which represents the biophysical limit of Earth's biosphere. Spores from a variety of species, including Aspergillus penicillioides , Eurotium halophilicum , Xerochrysium xerophilum (formerly Chrysosporium xerophilum ) and Xeromyces bisporus , were produced by cultures growing on media supplemented with glycerol (and contained up to 189 mg glycerol g dry spores −1 ). The ability of these spores to germinate, and the kinetics of germination, were then determined on a range of media designed to recreate stresses experienced in microbial habitats or anthropogenic systems (with water‐activities from 0.765 to 0.575). For A. penicillioides , Eurotium amstelodami , E. halophilicum , X. xerophilum and X. bisporus , germination occurred at lower water‐activities than previously recorded (0.640, 0.685, 0.651, 0.664 and 0.637 respectively). In addition, the kinetics of germination at low water‐activities were substantially faster than those reported previously. Extrapolations indicated theoretical water‐activity minima below these values; as low as 0.570 for A. penicillioides and X. bisporus . Glycerol is present at high concentrations (up to molar levels) in many types of microbial habitat. We discuss the likely role of glycerol in expanding the water‐activity limit for microbial cell function in relation to temporal constraints and location of the microbial cell or habitat. The findings reported here have also critical implications for understanding the extremes of Earth's biosphere; for understanding the potency of disease‐causing microorganisms; and in biotechnologies that operate at the limits of microbial function.

Recent declines in cancer incidence: related to the Great Recession? - Scarlett Lin Gomez; Alison J. Canchola; David O. Nelson; Theresa H. M. Keegan; Christina A. Clarke; Iona Cheng; Salma Shariff-Marco; Mindy DeRouen; Ralph Catalano; William A. Satariano; Kathleen Davidson-Allen; Sally L. Glaser (Cancer Causes & Control, 2017)

The Diagnosis and Natural History of Multiple System Atrophy, Cerebellar Type - David J. Lin; Katherine L. Hermann; Jeremy D. Schmahmann (The Cerebellum, 2016)

Microwave drying characteristics of microalgae (Chlorella vulgaris) for biofuel production - Al Rey C. Villagracia; Andres Philip Mayol; Aristotle T. Ubando; Jose Bienvenido Manuel M. Biona; Nelson B. Arboleda; Melanie Y. David; Roy B. Tumlos; Henry Lee; Ong Hui Lin; Rafael A. Espiritu; Alvin B. Culaba; Hideaki Kasai (Clean Technologies and Environmental Policy, 2016)

Nonsteroidal anti-inflammatory drugs, statins, and pancreatic cancer risk: a population-based case–control study - Pik Fang Kho; Jonathan Fawcett; Lin Fritschi; Harvey Risch; Penelope M. Webb; David C. Whiteman; Rachel E. Neale (Cancer Causes & Control, 2016)

Influence of Three Citrus Herbicides on Potential Production of Sorghum bicolor ‘Topper 76-6’ as a Bioenergy Crop - Patrick C. Wilson; Barrett Gruber; Youjian Lin; Prem Kumar; David Niebch; Sandra Wilson (Bulletin of Environmental Contamination and Toxicology, 2016)

A prognostic model for advanced colorectal neoplasia recurrence - Lin Liu; Karen Messer; John A. Baron; David A. Lieberman; Elizabeth T. Jacobs; Amanda J. Cross; Gwen Murphy; Maria Elena Martinez; Samir Gupta (Cancer Causes & Control, 2016)

Cortical thinning in former professional soccer players - Inga K. Koerte; Michael Mayinger; Marc Muehlmann; David Kaufmann; Alexander P. Lin; Denise Steffinger; Barbara Fisch; Boris-Stephan Rauchmann; Stefanie Immler; Susanne Karch; Florian R. Heinen; Birgit Ertl-Wagner; et al. (Brain Imaging and Behavior, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Extracellular Cl− regulates human SO4 2−/anion exchanger SLC26A1 by altering pH sensitivity of anion transport - Meng Wu; John F. Heneghan; David H. Vandorpe; Laura I. Escobar; Bai-Lin Wu; Seth L. Alper (Pflügers Archiv - European Journal of Physiology, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Residential cancer cluster investigation nearby a Superfund Study Area with trichloroethylene contamination - David J. Press; Meg McKinley; Dennis Deapen; Christina A. Clarke; Scarlett Lin Gomez (Cancer Causes & Control, 2016)

A cell wall-bound anionic peroxidase, PtrPO21, is involved in lignin polymerization in Populus trichocarpa - Chien-Yuan Lin; Quanzi Li; Sermsawat Tunlaya-Anukit; Rui Shi; Ying-Hsuan Sun; Jack P. Wang; Jie Liu; Philip Loziuk; Charles W. Edmunds; Zachary D. Miller; Ilona Peszlen; David C. Muddiman; et al. (Tree Genetics & Genomes, 2016)

Resolving the ancestry of Austronesian-speaking populations - Pedro A. Soares; Jean A. Trejaut; Teresa Rito; Bruno Cavadas; Catherine Hill; Ken Khong Eng; Maru Mormina; Andreia Brandão; Ross M. Fraser; Tse-Yi Wang; Jun-Hun Loo; Christopher Snell; et al. (Human Genetics, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Dopaminergic genetic variation moderates the effect of nicotine on cigarette reward - Paul T. Harrell; Hui-Yi Lin; Jong Y. Park; Melissa D. Blank; David J. Drobes; David E. Evans (Psychopharmacology, 2016)

Parallel evolution of leaf morphology in gnetophytes - Yong Yang; Longbiao Lin; David K. Ferguson (Organisms Diversity & Evolution, 2015)

Wave and Hydrodynamic Modeling for Engineering Design of Jetties at Tangier Island in Chesapeake Bay, USA - Lihwa Lin; Zeki Demirbilek; Donald Ward; David King (Journal of Marine Science and Engineering, 2015)
The protection of a boat canal at the western entrance of Tangier Island, Virginia, located in the lower Chesapeake Bay, is investigated using different structural alternatives. The existing entrance channel is oriented 45 deg with respect to the local shoreline, and exposed directly to the lower Bay without any protection. The adjacent shoreline has experienced progressive erosion in recent decades by flooding due to severe storms and waves. To protect the western entrance of the channel and shoreline, five different jetty and spur combinations were proposed to reduce wave energy in the lee of jetties. Environmental forces affecting the proposed jettied inlet system are quantified using the Coastal Modeling System, consisting of a spectral wave model and a depth-averaged circulation model with sediment transport calculations. Numerical simulations were conducted for design wave conditions and a 50-year return period tropical storm at the project site. Model results show a low crested jetty of 170-m length connecting to the north shore at a 45-deg angle, and a short south spur of 25-m long, provide adequate wave-reduction benefits among the five proposed alternatives. The model simulation indicates this alternative has the minimum impact on sedimentation around the structured inlet and boat canal.

Fully automatic and nonparametric quantification of adipose tissue in fat–water separation MR imaging - Defeng Wang; Lin Shi; Winnie C. W. Chu; Miao Hu; Brian Tomlinson; Wen-Hua Huang; Tianfu Wang; Pheng Ann Heng; David K. W. Yeung; Anil T. Ahuja (Medical & Biological Engineering & Computing, 2015)

Roles of the Fibrous Superficial Zone in the Mechanical Behavior of TMJ Condylar Cartilage - Leonardo Ruggiero; Brandon K. Zimmerman; Miri Park; Lin Han; Liyun Wang; David L. Burris; X. Lucas Lu (Annals of Biomedical Engineering, 2015)

Some of the people, some of the time: field evidence for associations and dissociations between stress and drug use - Melody Furnari; David H. Epstein; Karran A. Phillips; Michelle L. Jobes; William J. Kowalczyk; Massoud Vahabzadeh; Jia-Ling Lin; Kenzie L. Preston (Psychopharmacology, 2015)

Advanced neuroimaging applied to veterans and service personnel with traumatic brain injury: state of the art and potential benefits - Elisabeth A. Wilde; Sylvain Bouix; David F. Tate; Alexander P. Lin; Mary R. Newsome; Brian A. Taylor; James R. Stone; James Montier; Samuel E. Gandy; Brian Biekman; Martha E. Shenton; Gerald York (Brain Imaging and Behavior, 2015)

Methods and measurement variance for field estimations of coral colony planar area using underwater photographs and semi-automated image segmentation - Benjamin P. Neal; Tsung-Han Lin; Rivah N. Winter; Tali Treibitz; Oscar Beijbom; David Kriegman; David I. Kline; B. Greg Mitchell (Environmental Monitoring and Assessment, 2015)

Hyperglycemia down-regulates cGMP-dependent protein kinase I expression in first trimester cytotrophoblast cells - Tammy Nguyen; Saunders Lin; Ahmed F. Pantho; Belinda M. Kohl-Thomas; Madhava R. Beeram; David C. Zawieja; Thomas J. Kuehl; M. Nasir Uddin (Molecular and Cellular Biochemistry, 2015)

Association between Helicobacter pylori and pancreatic cancer risk: a meta-analysis - Annaka Schulte; Nirmala Pandeya; Jonathan Fawcett; Lin Fritschi; Harvey A. Risch; Penelope M. Webb; David C. Whiteman; Rachel E. Neale (Cancer Causes & Control, 2015)

A comparative meta-analysis of QTL between intraspecific Gossypium hirsutum and interspecific G. hirsutum × G. barbadense populations - Joseph I. Said; Mingzhou Song; Hantao Wang; Zhongxu Lin; Xianlong Zhang; David D. Fang; Jinfa Zhang (Molecular Genetics and Genomics, 2015)

A record-breaking low ice cover over the Great Lakes during winter 2011/2012: combined effects of a strong positive NAO and La Niña - Xuezhi Bai; Jia Wang; Jay Austin; David J. Schwab; Raymond Assel; Anne Clites; John F. Bratton; Marie Colton; John Lenters; Brent Lofgren; Trudy Wohlleben; Sean Helfrich; et al. (Climate Dynamics, 2015)

Stress signaling in response to polycyclic aromatic hydrocarbon exposure in Arabidopsis thaliana involves a nucleoside diphosphate kinase, NDPK-3 - Hong Liu; David Weisman; Ling Tang; Long Tan; Wen-ke Zhang; Zong-hua Wang; Yan-he Huang; Wen-xiong Lin; Xuan-ming Liu; Adán Colón-Carmona (Planta, 2015)

The phytotoxin coronatine is a multifunctional component of the virulence armament of Pseudomonas syringae - Xueqing Geng; Lin Jin; Mikiko Shimada; Min Gab Kim; David Mackey (Planta, 2014)

Differential Regulation of Lipid Metabolism Genes in the Brain of Acetylcholinesterase Knockout Mice - Huang-Quan Lin; Yan Wang; Kam-Leung Chan; Tsz-Ming Ip; Chi-Cheong David Wan (Journal of Molecular Neuroscience, 2014)

Composition of bacterial communities in sand dunes of subtropical coastal forests - Yu-Te Lin; William B. Whitman; David C. Coleman; Tsai-Huei Chen; Chih-Yu Chiu (Biology and Fertility of Soils, 2014)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

An ecological function and services approach to total maximum daily load (TMDL) prioritization - Robert K. Hall; David Guiliano; Sherman Swanson; Michael J. Philbin; John Lin; Joan L. Aron; Robin J. Schafer; Daniel T. Heggem (Environmental Monitoring and Assessment, 2014)

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

High Resolution 3-D Finite-Volume Coastal Ocean Modeling in Lower Campbell River and Discovery Passage, British Columbia, Canada - Yuehua Lin; David Fissel (Journal of Marine Science and Engineering, 2014)
The 3-D unstructured-grid, Finite-Volume Coastal Ocean Model (FVCOM) was used to simulate the flows in Discovery Passage including the adjoining Lower Campbell River, British Columbia, Canada. Challenges in the studies include the strong tidal currents (e.g., up to 7.8 m/s in Seymour Narrows) and tailrace discharges, small-scale topographic features and steep bottom slopes, and stratification affected by the Campbell River freshwater discharges. Two applications of high resolution 3-D FVCOM modeling were conducted. One is for the Lower Campbell River extending upstream as far as the John Hart Hydroelectric dam. The horizontal resolution varies from 0.27 m to 32 m in the unstructured triangular mesh to resolve the tailrace flow. The bottom elevation decreases ~14 m within the distance of ~1.4 km along the river. This pioneering FVCOM river modeling demonstrated a very good performance in simulating the river flow structures. The second application is to compute ocean currents immediately above the seabed along the present underwater electrical cable crossing routes across Discovery Passage. Higher resolution was used near the bottom with inter-layer spacing ranging from 0.125 to 0.0005 of total water depth. The model behaves very well in simulating the strong tidal currents in the area at high resolution in both the horizontal and vertical. One year maximum near bottom tidal current along the routes was then analyzed using the model results.

Unraveling the complex genetic model for cystic fibrosis: pleiotropic effects of modifier genes on early cystic fibrosis-related morbidities - Weili Li; David Soave; Melissa R. Miller; Katherine Keenan; Fan Lin; Jiafen Gong; Theodore Chiang; Anne L. Stephenson; Peter Durie; Johanna Rommens; Lei Sun; Lisa J. Strug (Human Genetics, 2014)

The N-glycoform of sRAGE is the key determinant for its therapeutic efficacy to attenuate injury-elicited arterial inflammation and neointimal growth - Hyun-Jin Tae; Ji Min Kim; Sungha Park; Noboru Tomiya; Geng Li; Wen Wei; Natalia Petrashevskaya; Ismayil Ahmet; John Pang; Stefanie Cruschwitz; Rebecca A. Riebe; Yinghua Zhang; et al. (Journal of Molecular Medicine, 2013)

Photosynthesis of temperate E ucalyptus globulus trees outside their native range has limited adjustment to elevated CO 2 and climate warming - Kristine Y. Crous; Audrey G. Quentin; Yan‐Shih Lin; Belinda E. Medlyn; David G. Williams; Craig V. M. Barton; David S. Ellsworth (Global Change Biology, 2013)
E ucalyptus species are grown widely outside of their native ranges in plantations on all vegetated continents of the world. We predicted that such a plantation species would show high potential for acclimation of photosynthetic traits across a wide range of growth conditions, including elevated [ CO 2 ] and climate warming. To test this prediction, we planted temperate E ucalyptus globulus Labill. seedlings in climate‐controlled chambers in the field located >700 km closer to the equator than the nearest natural occurrence of this species. Trees were grown in a complete factorial combination of elevated CO 2 concentration ( eC ; ambient [ CO 2 ] +240 ppm) and air warming treatments ( eT ; ambient +3 °C) for 15 months until they reached ca. 10 m height. There was little acclimation of photosynthetic capacity to eC and hence the CO 2 ‐induced photosynthetic enhancement was large (ca. 50%) in this treatment during summer. The warming treatment significantly increased rates of both carboxylation capacity ( V cmax ) and electron transport ( J max ) (measured at a common temperature of 25 °C) during winter, but decreased them significantly by 20–30% in summer. The photosynthetic CO 2 compensation point in the absence of dark respiration ( Γ *) was relatively less sensitive to temperature in this temperate eucalypt species than for warm‐season tobacco. The temperature optima for photosynthesis and J max significantly changed by about 6 °C between winter and summer, but without further adjustment from early to late summer. These results suggest that there is an upper limit for the photosynthetic capacity of E . globulus ssp. globulus outside its native range to acclimate to growth temperatures above 25 °C. Limitations to temperature acclimation of photosynthesis in summer may be one factor that defines climate zones where E . globulus plantation productivity can be sustained under anticipated global environmental change.

Twentieth century human and climate impacts on a large mountain lake in southwest China - Xinchun Guo; Aaron P. Potito; Lin Luo; David W. Beilman (Hydrobiologia, 2013)

Molecular basis for insecticide‐enhanced thermotolerance in the brown planthopper N ilaparvata lugens S tål ( H emiptera: D elphacidae) - Lin‐Quan Ge; Liu‐Juan Huang; Guo‐Qin Yang; Qi‐Sheng Song; David Stanley; G. M. Gurr; Jin‐Cai Wu (Molecular Ecology, 2013)
Climate change is likely to have marked ecological effects on terrestrial ecosystems, including the activities of insect pests. Most attention has focused on the increasing geographical ranges of pests; however, if extrinsic factors enhance their thermotolerance, populations may express increased voltinism and longer daily and annual activity periods. These changes in pest populations have the potential for severe consequences, including increased crop losses and decreased food security at the global level. The brown planthopper ( BPH ) Nilaparvata lugens Stål (Hemiptera: Delphacidae) is a serious pest of rice crops in temperate and tropical regions of Asia. It is often present in rice microclimates at temperatures close to its maximum thermotolerance. Recent BPH outbreaks in tropical Asia are considered to be associated with excess use of pesticides and increasing temperature. This study tested whether exposure to sublethal concentrations of triazophos (tzp), an insecticide widely used in Asian rice production, enhances thermotolerance of BPH . Tzp exposure (40 ppm at 40 °C) significantly decreased mortality (from 94% in controls to 50% at 48 h post‐treatment) and increased lethal mean time ( LT 50 ) of adults by 17.2 h. To investigate the underlying molecular mechanism of this tzp‐enhanced thermotolerance, we selected Hsp70 and Arginine kinase (Argk) for detailed study. Transcripts encoding both proteins in third‐instar nymphs and brachypterous adult females were up‐regulated, compared with controls, after exposure to tzp. RNA i silencing of both genes demonstrated that Hsp70 and Argk are essential for survival and tzp‐increased thermotolerance. We propose that tzp induces thermotolerance in BPH s by increasing the expression of genes that act in cell protection mechanisms. The significance of our proposal relates to the importance of understanding the influence of sublethal concentrations of insecticides on pest biology. In addition to its influence on thermotolerance, tzp also enhances BPH reproduction. We infer that exposure to a pesticide stressor can produce cross‐tolerance, that is, increased tolerance to one stressor also increases tolerance to other stressors, including temperature. Aside from needing a better understanding of these effects in nature and in other pest/cropping systems, we suggest that pest management programmes can be improved with better understanding of the influences of stressors, including increased environmental temperatures and sublethal concentrations of insecticides, on pest biology.

Nyamiviridae: Proposal for a new family in the order Mononegavirales - Jens H. Kuhn; Sadia Bekal; Yíngyún Caì; Anna N. Clawson; Leslie L. Domier; Marieke Herrel; Peter B. Jahrling; Hideki Kondo; Kris N. Lambert; Kathie A. Mihindukulasuriya; Norbert Nowotny; Sheli R. Radoshitzky; et al. (Archives of Virology, 2013)

Warming up to climate change: a participatory approach to engaging with agricultural stakeholders in the Southeast US - Wendy-Lin Bartels; Carrie A. Furman; David C. Diehl; Fred S. Royce; Daniel R. Dourte; Brenda V. Ortiz; David F. Zierden; Tracy A. Irani; Clyde W. Fraisse; James W. Jones (Regional Environmental Change, 2013)

Prediction of the In Vivo Force–Velocity Relationship of Slow Human Skeletal Muscle from Measurements in Myofibers - Sampath K. Gollapudi; David C. Lin (Annals of Biomedical Engineering, 2013)

Controlled Release of Simvastatin from In situ Forming Hydrogel Triggers Bone Formation in MC3T3-E1 Cells - Yoon Shin Park; Allan E. David; Kyung Min Park; Chia-Ying Lin; Khoi D. Than; Kyuri Lee; Jun Beom Park; Inho Jo; Ki Dong Park; Victor C. Yang (The AAPS Journal, 2013)

Identification and characterization of a novel scFv recognizing human and mouse CD133 - Suresh Kumar Swaminathan; Lin Niu; Nate Waldron; Steve Kalscheuer; David M. Zellmer; Michael R. Olin; John R. Ohlfest; Daniel A. Vallera; Jayanth Panyam (Drug Delivery and Translational Research, 2013)

Small fluctuations in the recovery of fusaria across consecutive sampling intervals with unmanned aircraft 100 m above ground level - Binbin Lin; Amir Bozorgmagham; Shane D. Ross; David G. Schmale III (Aerobiologia, 2013)

Water quality associated public health risk in Bo, Sierra Leone - David H. Jimmy; Abu J. Sundufu; Anthony P. Malanoski; Kathryn H. Jacobsen; Rashid Ansumana; Tomasz A. Leski; Umaru Bangura; Alfred S. Bockarie; Edries Tejan; Baochuan Lin; David A. Stenger (Environmental Monitoring and Assessment, 2013)

The novel Solanum tuberosum calcium dependent protein kinase, StCDPK3, is expressed in actively growing organs - Carolina Grandellis; Verónica Giammaria; Magalí Bialer; Franco Santin; Tian Lin; David J. Hannapel; Rita M. Ulloa (Planta, 2012)

Functional redundancy of the two 5-hydroxylases in monolignol biosynthesis of Populus trichocarpa: LC–MS/MS based protein quantification and metabolic flux analysis - Jack P. Wang; Christopher M. Shuford; Quanzi Li; Jina Song; Ying-Chung Lin; Ying-Hsuan Sun; Hsi-Chuan Chen; Cranos M. Williams; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2012)

Pharmacokinetic and Pharmacodynamic Modeling of Opioid-Induced Gastrointestinal Side Effects in Patients Receiving Tapentadol IR and Oxycodone IR - Xu Steven Xu; Mila Etropolski; David Upmalis; Akiko Okamoto; Rachel Lin; Partha Nandy (Pharmaceutical Research, 2012)

Islands of Ice: Influence of Free-Drifting Antarctic Icebergs on Pelagic Marine Ecosystems - Maria Vernet; Kenneth Smith; Adrián Cefarelli; John Helly; Ronald Kaufmann; Hai Lin; David Long; Alison Murray; Bruce Robison; Henry Ruhl; Timothy Shaw; Alana Sherman; et al. (Oceanography, 2012)

Neuromuscular complications in HIV: effects of aging - Jessica Robinson-Papp; Ik Lin Tan; David M. Simpson (Journal of NeuroVirology, 2012)

Chronic traumatic encephalopathy: neurodegeneration following repetitive concussive and subconcussive brain trauma - Christine M. Baugh; Julie M. Stamm; David O. Riley; Brandon E. Gavett; Martha E. Shenton; Alexander Lin; Christopher J. Nowinski; Robert C. Cantu; Ann C. McKee; Robert A. Stern (Brain Imaging and Behavior, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Vertical stratification of subsurface microbial community composition across geological formations at the Hanford Site - Xueju Lin; David Kennedy; Jim Fredrickson; Bruce Bjornstad; Allan Konopka (Environmental Microbiology, 2012)
Summary Microbial diversity in subsurface sediments at the Hanford Site 300 Area near Richland, Washington state (USA) was investigated by analysing 21 samples recovered from depths of 9–52 m. Approximately 8000 near full‐length 16S rRNA gene sequences were analysed across geological strata that include a natural redox transition zone. These strata included the oxic coarse‐grained Hanford formation, fine‐grained oxic and anoxic Ringold Formation sediments, and the weathered basalt group. We detected 1233 and 120 unique bacterial and archaeal OTUs (operational taxonomic units at the 97% identity level) respectively. Microbial community structure and richness varied substantially across the different geological strata. Bacterial OTU richness (Chao1 estimator) was highest (> 700) in the upper Hanford formation, and declined to about 120 at the bottom of the Hanford formation. Just above the Ringold oxic–anoxic interface, richness was about 325 and declined to less than 50 in the deeper reduced zones. The deeper Ringold strata were characterized by a preponderance ( c . 90%) of Proteobacteria . The bacterial community in the oxic sediments contained not only members of nine well‐recognized phyla but also an unusually high proportion of three candidate divisions (GAL15, NC10 and SPAM). Additionally, 13 novel phylogenetic orders were identified within the Deltaproteobacteria , a clade rich in microbes that carry out redox transformations of metals that are important contaminants on the Hanford Site.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Have Meteorological Conditions Reduced NO2 Concentrations from Local Emission Sources in Gothenburg? - Lin Tang; David Rayner; Marie Haeger-Eugensson (Water, Air, & Soil Pollution, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

A residue in the TRPM2 channel outer pore is crucial in determining species-dependent sensitivity to extracellular acidic pH - Jie Zou; Wei Yang; David J. Beech; Lin-Hua Jiang (Pflügers Archiv - European Journal of Physiology, 2011)

Trace metal cycling in the deep water of the South China Sea: The composition, sources, and fluxes of sinking particles - Tung-Yuan Ho; Wen-Chen Chou; Hui-Ling Lin; David D. Sheu (Limnology and Oceanography, 2011)
Moored sediment traps were deployed for 1 yr at depths of 120, 600, and 3500 m in the water column to investigate the trace metal (M) (Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn) composition, sources, and fluxes of deep‐water sinking particles. Vertical transport for most of the metals at 120 m was strongly associated with organic matter production, and the major part of many of the metals in the sinking particles was of anthropogenic origin. Although the lithogenic fraction in deeper waters greatly increased with depth, significant proportions of the nonlithogenic and nonintracellular fractions were still observed when using M : Al or M : P ratios as indicators, particularly for Zn, Cu, Ni, Co, and Mn. Because particles from horizontal transport and sediment resuspension are known to be lithogenic in the deep basin, the trace metals in sinking particles in the twilight zone and deep water, which feature significantly elevated M : Al ratios, originate from the downward transport of anthropogenic or authigenic origins. With increasing inputs from anthropogenic aerosols over large oceanic regions globally, the coupling and transport of some trace metals originating from anthropogenic aerosols, such as Zn, Cu, Co, and Ni, with sinking organic particles has become an important pathway for trace metal cycling not only in the euphotic zone, but also in the twilight zone and deeper waters.

A novel statistical method for classifying habitat generalists and specialists - Robin L. Chazdon; Anne Chao; Robert K. Colwell; Shang-Yi Lin; Natalia Norden; Susan G. Letcher; David B. Clark; Bryan Finegan; J. Pablo Arroyo (Ecology, 2011)
We develop a novel statistical approach for classifying generalists and specialists in two distinct habitats. Using a multinomial model based on estimated species relative abundance in two habitats, our method minimizes bias due to differences in sampling intensities between two habitat types as well as bias due to insufficient sampling within each habitat. The method permits a robust statistical classification of habitat specialists and generalists, without excluding rare species a priori. Based on a user‐defined specialization threshold, the model classifies species into one of four groups: (1) generalist; (2) habitat A specialist; (3) habitat B specialist; and (4) too rare to classify with confidence. We illustrate our multinomial classification method using two contrasting data sets: (1) bird abundance in woodland and heath habitats in southeastern Australia and (2) tree abundance in second‐growth (SG) and old‐growth (OG) rain forests in the Caribbean lowlands of northeastern Costa Rica. We evaluate the multinomial model in detail for the tree data set. Our results for birds were highly concordant with a previous nonstatistical classification, but our method classified a higher fraction (57.7%) of bird species with statistical confidence. Based on a conservative specialization threshold and adjustment for multiple comparisons, 64.4% of tree species in the full sample were too rare to classify with confidence. Among the species classified, OG specialists constituted the largest class (40.6%), followed by generalist tree species (36.7%) and SG specialists (22.7%). The multinomial model was more sensitive than indicator value analysis or abundance‐based phi coefficient indices in detecting habitat specialists and also detects generalists statistically. Classification of specialists and generalists based on rarefied subsamples was highly consistent with classification based on the full sample, even for sampling percentages as low as 20%. Major advantages of the new method are (1) its ability to distinguish habitat generalists (species with no significant habitat affinity) from species that are simply too rare to classify and (2) applicability to a single representative sample or a single pooled set of representative samples from each of two habitat types. The method as currently developed can be applied to no more than two habitats at a time.

Non-cancer mortality among people diagnosed with lymphohaematopoietic neoplasm in Australia - Peter D. Baade; Jill A. Royle; David J. Joske; Lin Fritschi (Cancer Causes & Control, 2011)

Probing Mechanical Adaptation of Neurite Outgrowth on a Hydrogel Material Using Atomic Force Microscopy - Frank Xue Jiang; David C. Lin; Ferenc Horkay; Noshir A. Langrana (Annals of Biomedical Engineering, 2011)

QTL analysis and candidate gene mapping for skin and flesh color in sweet cherry fruit (Prunus avium L.) - Suneth S. Sooriyapathirana; Amjad Khan; Audrey M. Sebolt; Dechun Wang; Jill M. Bushakra; Kui Lin-Wang; Andrew C. Allan; Susan E. Gardiner; David Chagné; Amy F. Iezzoni (Tree Genetics & Genomes, 2010)

Mechanism of the Specific Neuronal Toxicity of a Type I Ribosome-Inactivating Protein, Trichosanthin - Ou Sha; David Tai-Wai Yew; Eric Yu-Pang Cho; Tzi-Bun Ng; Lin Yuan; Wing-Hang Kwong (Neurotoxicity Research, 2010)

Bacterial community of very wet and acidic subalpine forest and fire-induced grassland soils - Yu-Te Lin; Ching-Ping Lin; Shu-Miaw Chaw; William B. Whitman; David C. Coleman; Chih-Yu Chiu (Plant and Soil, 2010)

ILCD Handbook Public Consultation Workshop - David W. Pennington; Kirana Chomkhamsri; Rana Pant; Marc-Andree Wolf; Giovanni Bidoglio; Klaus Kögler; Pavel Misiga; Michel Sponar; Bettina Lorz; Guido Sonnemann; Paolo Masoni; Hongtao Wang; et al. (The International Journal of Life Cycle Assessment, 2010)

The speed of mitochondrial movement is regulated by the cytoskeleton and myosin in Picea wilsonii pollen tubes - Maozhong Zheng; Qinli Wang; Yan Teng; Xiaohua Wang; Feng Wang; Tong Chen; Jozef Šamaj; Jinxing Lin; David C. Logan (Planta, 2010)

Sea level fluctuations on the east coast of Taiwan that overlie continental shelf break - David Ching-Fang Shih; Yue-Gau Chen; Gwo-Fong Lin; Yih-Min Wu; Yee-Ping Jia; Chih-Ming Ma (Stochastic Environmental Research and Risk Assessment, 2010)

Effect of the climate shift around mid 1970s on the relationship between wintertime Ural blocking circulation and East Asian climate - Lin Wang; Wen Chen; Wen Zhou; Johnny C. L. Chan; David Barriopedro; Ronghui Huang (International Journal of Climatology, 2010)
Blocking variability over the Ural Mountain region in the boreal winter and its relationship with the East Asian winter climate is investigated. The climate shift around mid 1970s has been shown to exert a significant influence on the blocking pattern. In contrast with the years before 1976/1977, the Ural blocking signal after 1976/1977 is found to propagate less into the stratosphere and more eastward in the troposphere to East Asia, which therefore exerts more influence on the East Asian winter climate. This enhanced Ural blocking–East Asian climate relationship amplifies the impact of Ural blocking on East Asia and, with the background of decreasing Ural blocking, contributes to the higher frequency of warm winters in this region. Further analyses suggest that the NAM‐related stratospheric polar vortex strength and its modulation on the propagation of atmospheric stationary waves can account for this change, with the key area being located in the North Atlantic region. Copyright © 2009 Royal Meteorological Society

Cocaine craving and use during daily life - Kenzie L. Preston; Massoud Vahabzadeh; John Schmittner; Jia-Ling Lin; David A. Gorelick; David H. Epstein (Psychopharmacology, 2009)

Therapeutic potential of olfactory ensheathing cells in neurodegenerative diseases - Shao-Chih Chiu; Huey-Shan Hung; Shinn-Zong Lin; Esheral Chiang; Demeral David Liu (Journal of Molecular Medicine, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Intercomparison, interpretation, and assessment of spring phenology in North America estimated from remote sensing for 1982–2006 - MICHAEL A. WHITE; KIRSTEN M. De BEURS; KAMEL DIDAN; DAVID W. INOUYE; ANDREW D. RICHARDSON; OLAF P. JENSEN; JOHN O'KEEFE; GONG ZHANG; RAMAKRISHNA R. NEMANI; WILLEM J. D. Van LEEUWEN; JESSLYN F. BROWN; ALLARD De WIT; et al. (Global Change Biology, 2009)
Shifts in the timing of spring phenology are a central feature of global change research. Long‐term observations of plant phenology have been used to track vegetation responses to climate variability but are often limited to particular species and locations and may not represent synoptic patterns. Satellite remote sensing is instead used for continental to global monitoring. Although numerous methods exist to extract phenological timing, in particular start‐of‐spring (SOS), from time series of reflectance data, a comprehensive intercomparison and interpretation of SOS methods has not been conducted. Here, we assess 10 SOS methods for North America between 1982 and 2006. The techniques include consistent inputs from the 8 km Global Inventory Modeling and Mapping Studies Advanced Very High Resolution Radiometer NDVIg dataset, independent data for snow cover, soil thaw, lake ice dynamics, spring streamflow timing, over 16 000 individual measurements of ground‐based phenology, and two temperature‐driven models of spring phenology. Compared with an ensemble of the 10 SOS methods, we found that individual methods differed in average day‐of‐year estimates by ±60 days and in standard deviation by ±20 days. The ability of the satellite methods to retrieve SOS estimates was highest in northern latitudes and lowest in arid, tropical, and Mediterranean ecoregions. The ordinal rank of SOS methods varied geographically, as did the relationships between SOS estimates and the cryospheric/hydrologic metrics. Compared with ground observations, SOS estimates were more related to the first leaf and first flowers expanding phenological stages. We found no evidence for time trends in spring arrival from ground‐ or model‐based data; using an ensemble estimate from two methods that were more closely related to ground observations than other methods, SOS trends could be detected for only 12% of North America and were divided between trends towards both earlier and later spring.

An Overview of Global Observing Systems Relevant to GODAE - Candyce Clark; D.E. Harrison; Mike Johnson; Graeme Ball; Howard Freeland; Gustavo Goni; Maria Hood; Michael McPhaden; David Meldrum; Mark Merrifield; Dean Roemmich; Chris Sabine; et al. (Oceanography, 2009)

An Atlas of ShakeMaps and population exposure catalog for earthquake loss modeling - Trevor I. Allen; David J. Wald; Paul S. Earle; Kristin D. Marano; Alicia J. Hotovec; Kuowan Lin; Michael G. Hearne (Bulletin of Earthquake Engineering, 2009)

Uncertainty propagation of hydrodispersive transfer in an aquifer: an illustration of one-dimensional contaminant transport with slug injection - David Ching-Fang Shih; Yue-Gau Chen; Gwo-Fong Lin; Yih-Min Wu (Stochastic Environmental Research and Risk Assessment, 2009)

Abnormal pain response in pain-sensitive opiate addicts after prolonged abstinence predicts increased drug craving - Zhen-Yu Ren; Jie Shi; David H. Epstein; Jun Wang; Lin Lu (Psychopharmacology, 2009)

A negative regulator encoded by a rice WRKY gene represses both abscisic acid and gibberellins signaling in aleurone cells - Zhong-Lin Zhang; Margaret Shin; Xiaolu Zou; Jianzhi Huang; Tun-hua David Ho; Qingxi J. Shen (Plant Molecular Biology, 2009)

Psychosocial stress after reactivation of drug-related memory impairs later recall in abstinent heroin addicts - Li-Yan Zhao; Xiao-Li Zhang; Jie Shi; David H. Epstein; Lin Lu (Psychopharmacology, 2009)

Myocardial oxidative stress, osteogenic phenotype, and energy metabolism are differentially involved in the initiation and early progression of δ-sarcoglycan-null cardiomyopathy - Comlan Missihoun; David Zisa; Arsalan Shabbir; Huey Lin; Techung Lee (Molecular and Cellular Biochemistry, 2009)

Ataxia and pancytopenia caused by a mutation in TINF2 - Elena Tsangaris; Sally-Lin Adams; Grace Yoon; David Chitayat; Peter Lansdorp; Inderjeet Dokal; Yigal Dror (Human Genetics, 2008)

Differential and combined impacts of extreme temperatures and air pollution on human mortality in south–central Canada. Part II: future estimates - Chad Shouquan Cheng; Monica Campbell; Qian Li; Guilong Li; Heather Auld; Nancy Day; David Pengelly; Sarah Gingrich; Joan Klaassen; Don MacIver; Neil Comer; Yang Mao; et al. (Air Quality, Atmosphere & Health, 2008)

Differential and combined impacts of extreme temperatures and air pollution on human mortality in south–central Canada. Part I: historical analysis - Chad Shouquan Cheng; Monica Campbell; Qian Li; Guilong Li; Heather Auld; Nancy Day; David Pengelly; Sarah Gingrich; Joan Klaassen; Don MacIver; Neil Comer; Yang Mao; et al. (Air Quality, Atmosphere & Health, 2008)

Global decomposition experiment shows soil animal impacts on decomposition are climate‐dependent - DIANA H. WALL; MARK A. BRADFORD; MARK G. ST. JOHN; JOHN A. TROFYMOW; VALERIE BEHAN‐PELLETIER; DAVID E. BIGNELL; J. MARK DANGERFIELD; WILLIAM J. PARTON; JOSEF RUSEK; WINFRIED VOIGT; VOLKMAR WOLTERS; HOLLEY ZADEH GARDEL; et al. (Global Change Biology, 2008)
Climate and litter quality are primary drivers of terrestrial decomposition and, based on evidence from multisite experiments at regional and global scales, are universally factored into global decomposition models. In contrast, soil animals are considered key regulators of decomposition at local scales but their role at larger scales is unresolved. Soil animals are consequently excluded from global models of organic mineralization processes. Incomplete assessment of the roles of soil animals stems from the difficulties of manipulating invertebrate animals experimentally across large geographic gradients. This is compounded by deficient or inconsistent taxonomy. We report a global decomposition experiment to assess the importance of soil animals in C mineralization, in which a common grass litter substrate was exposed to natural decomposition in either control or reduced animal treatments across 30 sites distributed from 43°S to 68°N on six continents. Animals in the mesofaunal size range were recovered from the litter by Tullgren extraction and identified to common specifications, mostly at the ordinal level. The design of the trials enabled faunal contribution to be evaluated against abiotic parameters between sites. Soil animals increase decomposition rates in temperate and wet tropical climates, but have neutral effects where temperature or moisture constrain biological activity. Our findings highlight that faunal influences on decomposition are dependent on prevailing climatic conditions. We conclude that (1) inclusion of soil animals will improve the predictive capabilities of region‐ or biome‐scale decomposition models, (2) soil animal influences on decomposition are important at the regional scale when attempting to predict global change scenarios, and (3) the statistical relationship between decomposition rates and climate, at the global scale, is robust against changes in soil faunal abundance and diversity.

Relationships between physiological responses and presyncope symptoms during tilting up in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2008)

Assessment of long-term variation in displacement for a GPS site adjacent to a transition zone between collision and subduction - David Ching-Fang Shih; Yih-Min Wu; Gwo-Fong Lin; Jyr-Ching Hu; Yue-Gau Chen; Chien-Hsin Chang (Stochastic Environmental Research and Risk Assessment, 2008)

Infrared heater arrays for warming ecosystem field plots - BRUCE A. KIMBALL; MATTHEW M. CONLEY; SHIPING WANG; XINGWU LIN; CAIYUN LUO; JACK MORGAN; DAVID SMITH (Global Change Biology, 2008)
There is a need for methodology to warm open‐field plots in order to study the likely effects of global warming on ecosystems in the future. Herein, we describe the development of arrays of more powerful and efficient infrared heaters with ceramic heating elements. By tilting the heaters at 45° from horizontal and combining six of them in a hexagonal array, good uniformity of warming was achieved across 3‐m‐diameter plots. Moreover, there do not appear to be obstacles (other than financial) to scaling to larger plots. The efficiency [ η h (%); thermal radiation out per electrical energy in] of these heaters was higher than that of the heaters used in most previous infrared heater experiments and can be described by: η h = 10 + 25exp(− 0.17 u ), where u is wind speed at 2 m height (m s − 1 ). Graphs are presented to estimate operating costs from degrees of warming, two types of plant canopy, and site windiness. Four such arrays were deployed over plots of grass at Haibei, Qinghai, China and another at Cheyenne, Wyoming, USA, along with corresponding reference plots with dummy heaters. Proportional integral derivative systems with infrared thermometers to sense canopy temperatures of the heated and reference plots were used to control the heater outputs. Over month‐long periods at both sites, about 75% of canopy temperature observations were within 0.5 °C of the set‐point temperature differences between heated and reference plots. Electrical power consumption per 3‐m‐diameter plot averaged 58 and 80 kW h day − 1 for Haibei and Cheyenne, respectively. However, the desired temperature differences were set lower at Haibei (1.2 °C daytime, 1.7 °C night) than Cheyenne (1.5 °C daytime, 3.0 °C night), and Cheyenne is a windier site. Thus, we conclude that these hexagonal arrays of ceramic infrared heaters can be a successful temperature free‐air‐controlled enhancement (T‐FACE) system for warming ecosystem field plots.

Development of a biofeedback tilt-table for investigating orthostatic syncope in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Embedded together: The life and death consequences of interaction of the Bcl-2 family with membranes - Brian Leber; Jialing Lin; David W. Andrews (Apoptosis, 2007)

Overexpression of proline oxidase induces proline-dependent and mitochondria-mediated apoptosis - Chien-an A. Hu; Steven P. Donald; Jian Yu; Wei-Wen Lin; Zhihe Liu; Gary Steel; Cassandra Obie; David Valle; James M. Phang (Molecular and Cellular Biochemistry, 2007)

Association analysis of SOD2 variants with methamphetamine psychosis in Japanese and Taiwanese populations - Kazuhiko Nakamura; Chih-Ken Chen; Yoshimoto Sekine; Yasuhide Iwata; A. Anitha; El-Wui Loh; Nori Takei; Atsuko Suzuki; Masayoshi Kawai; Kiyokazu Takebayashi; Katsuaki Suzuki; Yoshio Minabe; et al. (Human Genetics, 2006)

Phenotypic characterization of Bbs4 null mice reveals age-dependent penetrance and variable expressivity - Erica R. Eichers; Muhammad M. Abd-El-Barr; Richard Paylor; Richard Alan Lewis; Weimin Bi; Xiaodi Lin; Thomas P. Meehan; David W. Stockton; Samuel M. Wu; Elizabeth Lindsay; Monica J. Justice; Philip L. Beales; et al. (Human Genetics, 2006)

Climatic Change, Wars and Dynastic Cycles in China Over the Last Millennium - David D. Zhang; C. Y. Jim; George C-S Lin; Yuan-Qing He; James J. Wang; Harry F. Lee (Climatic Change, 2006)

α1-Adrenergic and α2-adrenergic balance in the dorsal pons and gross behavioral activity of mice in a novel environment - Eric A. Stone; Yan Lin; Mohammad R. Ahsan; David Quartermain (Psychopharmacology, 2005)

Characterization of Mesenchyme Homeobox 2 (MEOX2) transcription factor binding to RING finger protein 10 - Jijin Lin; Mona T. Friesen; Patricia Bocangel; David Cheung; Kathy Rawszer; Jeffrey T. Wigle (Molecular and Cellular Biochemistry, 2005)

The impact of on-farm water saving irrigation techniques on rice productivity and profitability in Zhanghe Irrigation System, Hubei, China - Piedad Moya; Lin Hong; David Dawe; Chen Chongde (Paddy and Water Environment, 2004)

RETINOIC ACID, BROMODEOXYURIDINE, AND THE Δ205 MUTANT POLYOMA VIRUS MIDDLE T ANTIGEN REGULATE EXPRESSION LEVELS OF A COMMON ENSEMBLE OF PROTEINS ASSOCIATED WITH EARLY STAGES OF INDUCING HL-60 LEUKEMIC CELL DIFFERENTIATION - ANDREW YEN; DAVID M. LIN; THOMAS J. LAMKIN; SUSI VARVAYANIS (In Vitro Cellular & Developmental Biology - Animal, 2004)

Surfactant proteinA and B genetic variants predispose to idiopathic pulmonary fibrosis - Moises Selman; Hung-Mo Lin; Martha Montao; Audrey L. Jenkins; Andrea Estrada; Zhenwu Lin; Guirong Wang; Susan L. DiAngelo; Xiaoxuan Guo; Todd M. Umstead; C. Max Lang; Annie Pardo; et al. (Human Genetics, 2003)

Disruption of plE2, the gene for the E2 subunit of the plastid pyruvate dehydrogenase complex, in Arabidopsis causes an early embryo lethal phenotype - Ming Lin; Robert Behal; David J. Oliver (Plant Molecular Biology, 2003)

Nuclear Transport by Laser-Induced Pressure Transients - Tai-Yuan David Lin; Daniel J. McAuliffe; Norm Michaud; Hong Zhang; Shun Lee; Apostolos G. Doukas; Thomas J. Flotte (Pharmaceutical Research, 2003)

Ferredoxin from sweet pepper (Capsicum annuum L.) intensifying harpinpss-mediated hypersensitive response shows an enhanced production of active oxygen species (AOS) - Badri Venkata Dayakar; Hao-Jan Lin; Cheng-Hsien Chen; Mang-Jye Ger; Bor- Heng Lee; Chia-Hwei Pai; David Chow; Hsiang-En Huang; Shaw-Yhi Hwang; Mei-Chu Chung; Teng-Yung Feng (Plant Molecular Biology, 2003)

Culture of isolated zygotic embryos of Pinus radiata D. Don. Part II: Biochemical changes associated with the conversion of isolated embryos - Xueqin Lin; David W. M. Leung (In Vitro Cellular & Developmental Biology - Plant, 2002)

Culture of isolated zygotic embryos of Pinus radiata D. Don. Part I: Factors influencing in vitro germination and growth of isolated embryos - Xueqin Lin; David W. M. Leung (In Vitro Cellular & Developmental Biology - Plant, 2002)

Software GPS Receiver - Vasu Chakravarthy; James Tsui; David Lin; John Schamus (GPS Solutions, 2001)

Time-dependent responses of soil CO2 efflux components to elevated atmospheric [CO2] and temperature in experimental forest mesocosms - Guanghui Lin; Paul T. Rygiewicz; James R. Ehleringer; Mark G. Johnson; David T. Tingey (Plant and Soil, 2001)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

cDNA cloning and characterization of a plant protein that may be associated with the harpinPSS-mediated hypersensitive response - Cheng-hsien Chen; Hao-jan Lin; Mang-jye Ger; David Chow; Teng-yung Feng (Plant Molecular Biology, 2000)

Characterization of three distinct cDNA clones encoding cysteine proteinases from maize (Zea mays L.) callus - Tibor Pechan; Binghua Jiang; David Steckler; Lijun Ye; Lei Lin; Dawn S. Luthe; W. Paul Williams (Plant Molecular Biology, 1999)

Competitive Inhibition of Glycylsarcosine Transport by Enalapril in Rabbit Renal Brush Border Membrane Vesicles: Interaction of ACE Inhibitors with High-Affinity H+/Peptide Symporter - Chun-Jung Lin; Wiyada Akarawut; David E. Smith (Pharmaceutical Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Picoplankton and nanoplankton and their trophic coupling in surface waters of the Sargasso Sea south of Bermuda - David A. Caron; Emily R. Peele; Ee Lin Lim; Mark R. Dennett (Limnology and Oceanography, 1999)
Studies were conducted during August and March–April in the Sargasso Sea south of Bermuda to examine rates of bacterial growth and picoplankton consumption by microbial consumers. Bacterial growth rates were estimated from [ 3 H]thymidine (TdR) incorporation rates, while grazing rates were determined using fluorescently labeled prey (FLP). In addition, net bacterial growth rates were calculated from changes in bacterial abundance during 24‐h incubations. The latter measurements were compared to net growth rates obtained by subtracting picoplankton grazing mortality rates from bacterial TdR growth rate estimates (TdR minus FLP). Overall, bacterial growth rates determined by TdR uptake were similar to FLP grazing rates during the March–April cruise, indicating an approximate balance between production and removal processes. Bacterial growth rates during August, however, were approximately twice the rates of grazer removal. Net bacterial growth rates determined from TdR growth rates minus FLP grazing rates were similar to net growth rates estimated from changes in abundance for samples collected near the surface during both cruises. However, rates of change of bacterial abundances during incubations were generally greater than rates predicted from TdR minus FLP for samples collected in the deep euphotic zone during both cruises. These discrepancies might be explained by several factors, including the inclusion of prochlorophytes in the bacterial counts and/or the stimulation of bacterial growth during containment. The TdR conversion factor also was an important consideration when comparing net bacterial growth rates estimated from changes in bacterial abundance to net growth rates determined from TdR minus FLP. Small nanoplanktonic protists (

Elevated CO 2 and temperature impacts on different components of soil CO 2 efflux in Douglas‐fir terracosms - Guanghui Lin; James R. Ehleringer; PauL. T. Rygiewicz; Mark G. Johnson; David T. Tingey (Global Change Biology, 1999)
Although numerous studies indicate that increasing atmospheric CO 2 or temperature stimulate soil CO 2 efflux, few data are available on the responses of three major components of soil respiration [i.e. rhizosphere respiration (root and root exudates), litter decomposition, and oxidation of soil organic matter] to different CO 2 and temperature conditions. In this study, we applied a dual stable isotope approach to investigate the impact of elevated CO 2 and elevated temperature on these components of soil CO 2 efflux in Douglas‐fir terracosms. We measured both soil CO 2 efflux rates and the 13 C and 18 O isotopic compositions of soil CO 2 efflux in 12 sun‐lit and environmentally controlled terracosms with 4‐year‐old Douglas fir seedlings and reconstructed forest soils under two CO 2 concentrations (ambient and 200 ppmv above ambient) and two air temperature regimes (ambient and 4 °C above ambient). The stable isotope data were used to estimate the relative contributions of different components to the overall soil CO 2 efflux. In most cases, litter decomposition was the dominant component of soil CO 2 efflux in this system, followed by rhizosphere respiration and soil organic matter oxidation. Both elevated atmospheric CO 2 concentration and elevated temperature stimulated rhizosphere respiration and litter decomposition. The oxidation of soil organic matter was stimulated only by increasing temperature. Release of newly fixed carbon as root respiration was the most responsive to elevated CO 2 , while soil organic matter decomposition was most responsive to increasing temperature. Although some assumptions associated with this new method need to be further validated, application of this dual‐isotope approach can provide new insights into the responses of soil carbon dynamics in forest ecosystems to future climate changes.

The ecology of Paraphysomonas imperforata based on studies employing oligonucleotide probe identification in coastal water samples and enrichment cultures - Ee Lin Lim; Mark R. Dennett; David A. Caron (Limnology and Oceanography, 1999)
The geographical distribution and seasonal abundance of the cosmopolitan heterotrophic flagellate Paraphysomonas imperforata in several coastal waters was examined using species‐specific oligonucleotide hybridization probes which target small subunit ribosomal RNA. P. imperforata was found to occur in several coastal environments, but at very low abundances (typically −1 ). The seasonal abundance of P. imperforata examined at one sampling site remained consistently low and constituted no more than 1% of the total nanoplankton at any time during a 17‐month sampling period. In contrast to the low abundances observed in natural water samples, P. imperforata frequently dominated heterotrophic enrichment cultures prepared from these same samples, comprising up to 98% of the total nanoplankton. Based on these findings, we conclude that P. imperforata is an opportunistic species capable of growing rapidly to high abundances when prey concentrations are high. Water and enrichment temperature as well as the temperature tolerance range of P. imperforata appear to have played a role in the seasonal differences observed in P. imperforata dominance. Experiments with enrichment cultures indicated that the absolute abundances of P. imperforata in the water samples and the activity of consumers of nanoplankton also influenced the degree to which P. imperforata dominated the heterotrophic nanoplankton assemblages of enrichment cultures. Seasonal changes in water temperature might also affect these latter factors, and, as a consequence, indirectly influence the ability of P. imperforata populations to dominate enrichments. Our results support the notion that enrichment cultivation of heterotrophic flagellates, and perhaps incubations in general, can select for species such as P. imperforata that may not be representative of nanoplanktonic protists that numerically dominate natural assemblages.

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Suggestive evidence for linkage of schizophrenia to markers on chromosome 13 in Caucasian but not Oriental populations - M.-W. Lin; P. Sham; Hai-Gwo Hwu; David Collier; Robin Murray; John F. Powell (Human Genetics, 1997)

Synthesis of RNA with relation to aging inRhizoctonia solani - F. L. Davies; F. K. Lin; David Gottlieb (Archives of Microbiology, 1974)